Curable composition
By using acrylic monomers and acrylic polymer components in thermally conductive materials and combining fillers, the problems of poor storage stability and brittleness of existing thermally conductive materials in high humidity environments are solved, and the rapid curing of room temperature and excellent adhesiveness in high humidity environments are achieved. Combination and thermal conductivity are suitable for thermal management applications such as battery modules.
Patent Information
- Application Number
- CN202180061911.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-18
- Filing Date
- 2021-08-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-08-26
AI Technical Summary
The existing thermally conductive materials have poor storage stability in high humidity environments, are brittle and low adhesion, making them difficult to cure quickly at room temperature, affecting their application in thermal management such as battery modules.
A curable composition containing acrylic monomer and acrylic polymer components was developed to ensure rapid curing at room temperature and maintain excellent adhesion and thermal conductivity in high humidity environments by adjusting component proportions and adding fillers. , forming a flexible but not brittle cured product.
It achieves rapid curing at room temperature and maintains excellent adhesion and thermal conductivity in high humidity environments, ensures the flexibility and durability of the cured products, and is suitable for thermal management applications such as battery modules.
Smart Images

Figure SMS_6 
Figure SMS_7 
Figure SMS_8
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2020-0127537 filed on September 29, 2020 and Korean Patent Application No. 10-2021-0109008 filed on August 18, 2021, the disclosures of which are incorporated herein by reference in their entirety. Technical Field
[0004] The present application relates to curable compositions. Background Art
[0005] As the handling of heat generated by electric products, electronic products, or batteries such as secondary batteries becomes an important issue, various heat dissipation countermeasures have been proposed.
[0006] Among thermally conductive materials used as heat dissipation countermeasures, resin compositions in which thermally conductive fillers are blended with resins are known.
[0007] In Patent Document 1 (Korean Patent Application Laid-Open No. 10-2016-0105354), a battery module to which such a resin composition is applied is known.
[0008] Among known resins, a typical resin having excellent heat resistance is a silicone resin, so that in such materials, a silicone resin is generally used as the resin.
[0009] However, since the silicone resin has poor adhesive force, there is a problem that the use of the resin composition is limited.
[0010] Thermally conductive resin compositions applied with polyurethane having excellent adhesion are also known. However, since polyurethane-based materials are susceptible to moisture or humidity, resin compositions applied with them have poor storage stability and are not easy to ensure appropriate curability during high humidity periods such as rainy seasons. Summary of the invention
[0011] Technical issues
[0012] An object of the present application is to provide a curable composition having excellent resistance to moisture and humidity, thereby ensuring excellent storage stability regardless of environmental changes.
[0013] Furthermore, an object of the present application is to provide a curable composition which exhibits room temperature curability and rapid curability in a high humidity environment even if it contains an excessive amount of a filler composition.
[0014] Furthermore, it is an object of the present application to provide a curable composition that exhibits appropriate viscosity, thixotropy, adhesion and / or thermal conductivity before and after curing.
[0015] Furthermore, an object of the present application is to provide a curable composition capable of forming a flexible cured product without brittleness by adjusting the hardness.
[0016] Technical Solution
[0017] Among the physical properties mentioned in this application, when measuring the temperature-affected physical properties, unless otherwise specified, the relevant physical properties are the physical properties measured at room temperature.
[0018] The term room temperature as used herein is a natural temperature without warming or cooling, which may mean, for example, any temperature in the range of 10°C to 30°C, for example, a temperature of about 15°C or higher, about 18°C or higher, about 20°C or higher, about 23°C or higher, about 27°C or lower, or 25°C.
[0019] As used herein, the term 'a to b' means 'within the range of a to b, including both a and b'. For example, the fact that a to b parts by weight is included has the same meaning as comprising in the range of a to b parts by weight.
[0020] The term relative humidity as used herein is expressed as a percentage (%) of the amount of water vapor contained in a unit volume of current air to the saturated vapor pressure that the unit volume of air can contain at a maximum, which may be expressed as RH%.
[0021] As used herein, the term weight average molecular weight (M w ) and number average molecular weight (M n ) can be measured using GPC (gel permeation chromatography), and specifically can be measured according to the following physical property measurement method. In addition, as used herein, the term polydispersity index (PDI) is obtained by dividing the weight average molecular weight (M w ) divided by the number average molecular weight (M n ) and the value (M w / M n ), which refers to the molecular weight distribution of the polymer. Specifically, the number average molecular weight (M n ) and weight average molecular weight (M w) It can be measured as follows: Place the analyte in a 20 mL vial, dilute it to a concentration of about 20 mg / mL in a THF (tetrahydrofuran) solvent, and then filter the standard sample for calibration and the sample to be analyzed through a syringe filter (pore size: 0.2 μm). In addition, as an analysis procedure, ChemStation of Agilent technologies can be used, and the number-average molecular weight (M n ) and the weight-average molecular weight (M w ) can be obtained by comparing the elution time of the sample with the calibration curve. Here, the polydispersity index (PDI) can be the value obtained by dividing the measured weight-average molecular weight (M w ) by the number-average molecular weight (M n ).
[0022] <GPC Measurement Conditions>
[0023] Instrument: 1200 series of Agilent technologies
[0024] Column: Use TL Mix.A&B of Agilent technologies
[0025] Solvent: THF
[0026] Column temperature: 40 °C
[0027] Sample concentration: 20 mg / mL, inject 10 μL
[0028] Use MP: 364000, 91450, 17970, 4910 and 1300 as standard samples
[0029] The term viscosity as used herein can be the value measured at room temperature, and specifically can be measured according to the following viscosity measurement method.
[0030] [Viscosity Measurement Method]
[0031] The viscosity of the curable composition can be measured using a viscometer (manufacturer: Brookfield, model name: Brookfield AMETEK / DV3T) and spindle 63. After zeroing the viscometer, install the spindle on the spindle connection part of the viscometer. Install the plate on the plate connection part of the viscometer and adjust it with the adjusting rod to form a certain gap between the spindle and the plate. Separate the plate and apply about 0.5 mL of the measurement target (for example, curable composition or acrylic polymer component, etc.) to the center of the separated plate. Reinstall the plate with the measurement target on the plate connection part of the viscometer, and after waiting until the torque value becomes 0, measure the viscosity at about 25 °C and a rotational speed of 15 rpm.
[0032] The term thermal conductivity as used herein may be measured in a state where the curable composition is prepared as a sample (cured product) having a diameter of 2 cm or more and a thickness of 500 μm according to ASTM D5470 standard or ISO 22007-2 standard along a thickness direction of the sample. The term excellent thermal conductivity (or excellent thermal conductivity) as used herein may mean a thermal conductivity of about 1.2 W / mK or more, 1.3 W / mK or more, 1.4 W / mK or more, 1.5 W / mK or more, 1.6 W / mK or more, 1.7 W / mK or more, 1.8 W / mK or more, 1.9 W / mK or more, 2.0 W / mK or more, 2.1 W / mK or more, 2.2 W / mK or more, 2.3 W / mK or more, 2.4 W / mK or more, 2.5 W / mK or more, 2.6 W / mK or more, 2.7 W / mK or more, 2.8 W / mK or more, 2.9 W / mK or more, or 3.0 W / mK or more as measured according to the above measurement method.
[0033] The term substitution as used herein means that a hydrogen atom bonded to a carbon atom of a compound is changed to another substituent, wherein the position of the substitution is not particularly limited as long as it is a position where the hydrogen atom is substituted (i.e., a position where the substituent is substitutable), and when two or more substituents are substituted, the substituents may be the same as or different from each other.
[0034] The term substituent as used herein means an atom or atom group replacing one or more hydrogen atoms on the parent chain of a hydrocarbon. In addition, substituents are described below, but are not limited thereto, and unless otherwise specified herein, substituents may further be substituted with the substituent described below or may not be substituted with any substituent.
[0035] Unless otherwise described, the term alkyl or alkylene as used herein can be a linear or branched alkyl or alkylene group having 1 to 20 carbon atoms, or 1 to 16 carbon atoms, or 1 to 12 carbon atoms, or 1 to 8 carbon atoms, or 1 to 6 carbon atoms, or a cyclic alkyl or alkylene group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms. Here, cyclic alkyl or alkylene group also includes alkyl or alkylene group only having a ring structure, and alkyl or alkylene group containing a ring structure. For example, cyclohexyl and methylcyclohexyl both correspond to cyclic alkyl groups. In addition, for example, the alkyl group or alkylene group can be specifically exemplified by (methylene), (ethylene), (n-propylene), (isopropylene), (n-butyl), (isobutyl), (tert-butyl), (sec-butyl, 1-methyl- (butyl), 1-ethyl- (butyl), (n-pentyl), (isopentyl), (neopentyl, (tert-pentyl), (n-hexyl, 1-methylpentyl, 2-methylpentyl, 4-methyl-2-pentyl, 3,3- -dimethylbutylene, 2-ethylbutylene, n-heptyl, 1-methylhexyl, n-octyl, tert-octyl, 1-methylheptyl, 2-ethylhexyl, 2-propylpentyl, n-nonyl, 2,2-dimethylheptyl, 1-ethylpropylene, 1,1-dimethylpropylene, isohexyl, 2-methylpentyl, 4-methylhexyl, 5-methylhexyl, etc., but are not limited thereto. In addition, the cycloalkyl or cycloalkylene group can be specifically exemplified by cyclopropyl, cyclobutyl, cyclopentyl, 3-methylcyclopentyl, 2,3-dimethylcyclopentyl, cyclohexyl, 3-methylcyclohexyl, 4-methylcyclohexyl, 2,3-dimethylcyclohexyl, 3,4,5-trimethylcyclohexyl, 4-tert-butylcyclohexyl, cycloheptyl, cyclooctyl, etc., but are not limited thereto.
[0036] Unless otherwise described, the term alkenyl or alkenylene as used herein can be a linear or branched acyclic alkenyl or alkenylene having 2 to 20 carbon atoms, or 2 to 16 carbon atoms, or 2 to 12 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms, or a cyclic alkenyl or alkenylene having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms. Here, when alkenyl or alkenylene having a ring structure is included, it corresponds to a cyclic alkenyl or alkenylene. In addition, for example, it can be exemplified by vinylene, n-propenylene, isopropenylene, n-butenylene, isobutenylene, tert-butenylene, sec-butenylene, 1-methyl-butenylene, 1-ethyl-butenylene, n-pentenylene, isopentenylene, neopentenylene, tert-pentenylene, n-hexenylene, 1-methylpentenylene, 2-methylpentenylene, 4-methyl-2-pentenylene, 3,3-dimethylpentenylene, butenyl, 2-ethylbutenyl, n-heptenyl, 1-methylhexenyl, n-octenyl, tert-octenyl, 1-methylheptenyl, 2-ethylhexenyl, 2-propylpentenyl, n-nonenyl, 2,2-dimethylheptenyl, 1-ethylpropenyl, 1,1-dimethylpropenyl, isohexenyl, 2-methylpentenyl, 4-methylhexenyl, 5-methylhexenyl, etc., but are not limited thereto. In addition, the cycloalkenyl group or cycloalkenylene group can be specifically exemplified by cyclopropenyl, cyclobutenyl, cyclopentenyl, 3-methylcyclopentenyl, 2,3-dimethylcyclopentenyl, cyclohexenyl, 3-methylcyclohexenyl, 4-methylcyclohexenyl, 2,3-dimethylcyclohexenyl, 3,4,5-trimethylcyclohexenyl, 4-tert-butylcyclohexenyl, cycloheptenyl, cyclooctenyl, etc., but are not limited thereto.
[0037] Unless otherwise described, the term alkynyl or alkynylene as used herein can be a linear or branched acyclic alkynyl or alkynylene having 2 to 20 carbon atoms, or 2 to 16 carbon atoms, or 2 to 12 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms, or can be a cyclic alkynyl or alkynylene having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms. Herein, when an alkynyl or alkynylene having a ring structure is included, it corresponds to a cyclic alkynyl or alkynylene. In addition, for example, it can be exemplified by an ethynyl group, a n-propynyl group, an isopropynyl group, a n-butynyl group, an isobutynyl group, a tert-butynyl group, a sec-butynyl group, a 1-methyl-butynyl group, a 1-ethyl-butynyl group, a n-pentynyl group, an isopentenyl group, a neopentynyl group, a tert-pentynyl group, a n-hexynyl group, a 1-methylpentynyl group, a 2-methylpentynyl group, a 4-methyl-2-pentynyl group, a 3,3-dimethylpentynyl group, a butynyl, 2-ethylbutynyl, n-heptynyl, 1-methylhexynyl, n-octynyl, tert-octynyl, 1-methylheptynyl, 2-ethylhexynyl, 2-propylpentynyl, n-nonynyl, 2,2-dimethylheptynyl, 1-ethylpropynyl, 1,1-dimethylpropynyl, isohexynyl, 2-methylpentynyl, 4-methylhexynyl, 5-methylhexynyl, etc., but are not limited thereto. In addition, the cycloalkynyl group or cycloalkynylene group can be specifically exemplified by cyclopropynyl, cyclobutynyl, cyclopentynyl, 3-methylcyclopentynyl, 2,3-dimethylcyclopentynyl, cyclohexynyl, 3-methylcyclohexynyl, 4-methylcyclohexynyl, 2,3-dimethylcyclohexynyl, 3,4,5-trimethylcyclohexynyl, 4-tert-butylcyclohexynyl, cycloheptynyl, cyclooctynyl, etc., but are not limited thereto.
[0038] Alkyl, alkylene, alkenyl, alkenylene, alkynyl and alkynylene may also be optionally substituted with one or more substituents. In this case, the substituent may be one or more selected from the group consisting of halogen (chlorine (Cl), iodine (I), bromine (Br), fluorine (F)), aryl, heteroaryl, epoxy, alkoxy, cyano, carboxyl, acryloyl, methacryloyl, acryloyloxy, methacryloyloxy, carbonyl and hydroxyl, but is not limited thereto.
[0039] As used herein, the term aryl means an aromatic ring wherein a hydrogen is removed from an aromatic hydrocarbon ring, wherein the aromatic hydrocarbon ring may include a monocyclic or polycyclic ring. Unless otherwise described, aryl does not have a particularly limited number of carbon atoms, but may be an aryl having 6 to 30 carbon atoms, or 6 to 26 carbon atoms, or 6 to 22 carbon atoms, or 6 to 20 carbon atoms, or 6 to 18 carbon atoms, or 6 to 15 carbon atoms. In addition, as used herein, the term arylidene means that aryl has two bonding positions, that is, a divalent group. The description of aryl as described above may be applied, except that arylidene is each a divalent group. Aryl may be exemplified as, for example, phenyl, phenylethyl, phenylpropyl, benzyl, tolyl, xylyl or naphthyl, but is not limited thereto.
[0040] As used herein, the term heteroaryl is an aromatic ring comprising one or more heteroatoms other than carbon, which may specifically include one or more heteroatoms selected from nitrogen (N), oxygen (O), sulfur (S), selenium (Se) and tellurium (Te). In this case, the atom constituting the ring structure of heteroaryl may be referred to as ring atoms. In addition, heteroaryl may include monocycle or polycycle. Unless otherwise described, heteroaryl does not have a particularly restricted number of carbon atoms, but may be a heteroaryl having 2 to 30 carbon atoms, or 2 to 26 carbon atoms, or 2 to 22 carbon atoms, or 2 to 20 carbon atoms, or 2 to 18 carbon atoms, or 2 to 15 carbon atoms. In another example, heteroaryl does not have a particularly restricted number of ring atoms, but may be a heteroaryl having 5 to 30, 5 to 25, 5 to 20, 5 to 15, 5 to 10, or 5 to 8 ring atoms. The heteroaryl group can be exemplified by, for example, thienyl, furyl, pyrrolyl, imidazolyl, thiazolyl, Azolyl, oxadiazolyl, triazolyl, pyridyl, bipyridyl, pyrimidyl, triazinyl, acridinyl, pyridazinyl, pyrazinyl, quinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, pyrazinopyrazinyl, isoquinolyl, indolyl, carbazolyl, benzo oxazolyl, benzimidazolyl, benzothiazolyl, benzocarbazolyl, dibenzocarbazolyl, benzothiophenyl, dibenzothiophenyl, benzofuranyl, dibenzofuranyl, benzothiorolyl, dibenzothiorolyl, phenanthroline, isothiophene Azolyl, thiadiazolyl, phenothiazinyl, phen Azine group and its condensed structure, etc., but are not limited thereto.
[0041] In addition, the term heteroarylene as used herein means that the heteroaryl group has two bonding positions, that is, a divalent group. The description of the heteroaryl group as described above can be applied, except that each heteroarylene group is a divalent group.
[0042] The aryl or heteroaryl group may also be optionally substituted with one or more substituents. In this case, the substituent may be one or more selected from the following: halogen (chlorine (Cl), iodine (I), bromine (Br), fluorine (F)), aryl, heteroaryl, epoxy, alkoxy, cyano, carboxyl, acryloyl, methacryloyl, acryloyloxy, methacryloyloxy, carbonyl and hydroxyl, but is not limited thereto.
[0043] The term (meth)acrylate as used herein means acrylate and methacrylate, and specifically means acrylic acid, methacrylic acid, a derivative of acrylic acid, or a derivative of methacrylic acid.
[0044] The term (meth)acrylate as used herein may be represented by a compound represented by Formula 1 below.
[0045] [Formula 1]
[0046]
[0047] In the above formula 1, R1 may be hydrogen or an alkyl group having 1 to 20 carbon atoms. In addition, R2 may be hydrogen or halogen (fluorine (F), chlorine (Cl), iodine (I), bromine (Br)), an alkyl group which is unsubstituted or substituted by the above substituents, an alkenyl group which is unsubstituted or substituted by the above substituents, an alkynyl group which is unsubstituted or substituted by the above substituents, an aryl group which is unsubstituted or substituted by the above substituents, a heteroaryl group which is unsubstituted or substituted by the above substituents, or a hydroxyl group.
[0048] In Formula 1, when R1 is hydrogen and R2 is hydrogen, it is acrylic acid, and when R1 is methyl and R2 is hydrogen, it is methacrylic acid.
[0049] Furthermore, in Formula 1, when R1 is hydrogen and R2 is not hydrogen, it may be referred to as an acrylic acid derivative; and when R1 is a methyl group and R2 is not hydrogen, it may be referred to as a methacrylic acid derivative.
[0050] The compound of Formula 1 can be exemplified by, for example, (meth)acrylic acid; alkyl (meth)acrylates including methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and stearyl (meth)acrylate; aryl (meth)acrylates including phenyl (meth)acrylate, 3-phenoxypropyl (meth)acrylate, and nonylphenol ethylene oxide-modified (meth)acrylate; ether-based (meth)acrylates including methoxymethyl (meth)acrylate, ethoxymethyl (meth)acrylate, propoxymethyl (meth)acrylate, butoxymethyl (meth)acrylate, isobutyloxymethyl (meth)acrylate, and butyloxymethyl (meth)acrylate. Esters, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, oxirane (meth)acrylate, oxetane (meth)acrylate, tetrahydrofuran (meth)acrylate, tetrahydro-2H-pyran (meth)acrylate, oxirane methyl (meth)acrylate (or glycidyl (meth)acrylate), oxetane ethyl (meth)acrylate and tetrahydrofuranyl methyl (meth)acrylate (or tetrahydrofurfuryl (meth)acrylate); hydroxyl-containing (Meth)acrylates, including 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, 2,2-dihydroxyethyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, alkoxy polyethylene glycol mono(meth)acrylate and alkoxy polypropylene glycol mono(meth)acrylate; and the like, but are not limited thereto.
[0051] The term monomer component as used herein means a component in which the polymerizable monomer ratio is 55 wt % or more, 55 wt % or more, 65 wt % or more, 75 wt % or more, 85 wt % or more, 95 wt % or more, or 99 wt % or more, relative to the total weight, or it is 100 wt %. The upper limit of the polymerizable monomer ratio is not particularly limited, for example, the ratio may be about 100 wt % or less.
[0052] The term acrylic monomer component as used herein means a component in which the content ratio of (meth)acrylic acid ester is 55 wt % or more, 55 wt % or more, 65 wt % or more, 75 wt % or more, 85 wt % or more, 95 wt % or more, or 99 wt % or more, or it is 100 wt %. The upper limit of the polymerizable monomer ratio is not particularly limited, for example, the ratio may be about 100 wt % or less.
[0053] The term acrylic polymer component as used herein means a component formed by polymerization of a monomer mixture in which the content ratio of the acrylic monomer component is 55 wt % or more, 55 wt % or more, 65 wt % or more, 75 wt % or more, 85 wt % or more, 95 wt % or more, or 99 wt % or more, or it is 100 wt %. The upper limit of the ratio of the acrylic monomer component is not particularly limited, and for example, the ratio may be about 100 wt % or less.
[0054] Curable composition
[0055] The curable composition according to one example of the present application may include a filler composition, an acrylic monomer component, and an acrylic polymer component.
[0056] The term curable composition as used herein may include components that can be converted into resins by curing reactions or polymerization reactions and components that are generally referred to as resins. In addition, the curable composition may be an adhesive composition, that is, an adhesive itself or a composition that can form an adhesive by a reaction such as a curing reaction.
[0057] Furthermore, the curable composition may be a solvent-based curable composition, a water-based curable composition, or a solvent-free curable composition.
[0058] In addition, the curable composition can be an active energy ray (e.g., ultraviolet) curable type, a moisture curable type, a heat curable type, or a room temperature curable type, and preferably, the curable composition can be a room temperature curable type composition. When the curable composition is an active energy ray curable type, the curing of the curable composition is performed by irradiating with active energy rays such as ultraviolet rays; when it is a moisture curable type, the curing of the curable composition is performed by a method of keeping it at an appropriate humidity; when it is a heat curable type, the curing of the curable composition is performed by a method of applying appropriate heat; or when it is a room temperature curable type, the curing of the curable composition is performed by a method of keeping the curable composition at room temperature.
[0059] In a curable composition according to an example of the present application, one or more of the polymerization units selected from the acrylic polymer component and the acrylic monomer component may include an acrylic compound based on a cyclic ether. Specifically, in a curable composition according to an example of the present application, the acrylic monomer component may include an acrylic compound based on a cyclic ether. In addition, in a curable composition according to an example of the present application, the polymerization units of the acrylic polymer component may include an acrylic compound based on a cyclic ether. In addition, in a curable composition according to an example of the present application, the acrylic monomer component and the acrylic polymer component may include an acrylic compound based on a cyclic ether.
[0060] In the present application, the meaning of "a polymerization unit of an acrylic polymer component contains a specific compound" is that the acrylic polymer component has been formed by polymerizing a monomer composition containing the specific compound, which specifically means that a structure derived from the specific compound is contained as a polymerization unit of the acrylic polymer component. That is, the meaning of "a polymerization unit of an acrylic polymer component contains a cyclic ether-based acrylic compound" is that the acrylic polymer component has been formed by polymerizing a monomer composition containing a cyclic ether-based acrylic compound, which means that a structure derived from a cyclic ether-based acrylic compound is contained as a polymerization unit.
[0061] In addition, in the present application, the meaning of the polymerization unit of the acrylic polymer component containing a specific compound at a specific weight % is that the acrylic polymer component has been formed by polymerizing a monomer composition containing a specific compound at a specific weight %, which specifically means that as a polymerization unit of the acrylic polymer component, a structure derived from a specific compound at a specific weight %. In addition, in the present application, the meaning of the total weight of the polymerization unit of the acrylic polymer component may mean the total weight of the monomer composition when the acrylic polymer component is formed by polymerizing a monomer composition containing one or more compounds at each content ratio.
[0062] Relative to gross weight, the curable composition according to an example of the present application can include an acrylic polymer component in an amount of 2.5 wt % or more, 2.6 wt % or more, 2.7 wt % or more, 2.8 wt % or more, or 2.9 wt % or more. In addition, in another example, relative to gross weight, the curable composition can include an acrylic polymer component in an amount of 5.5 wt % or less, 5.4 wt % or less, 5.3 wt % or less, 5.2 wt % or less, or 5.1 wt % or less. The content ratio of the acrylic polymer component in the curable composition can be within the range formed by appropriately selecting the upper and lower limits listed above.
[0063] The curable composition according to one example of the present application may form a cured product having excellent thermal conductivity and hardness by including the acrylic polymer component within the content ratio.
[0064] The curable composition according to one example of the present application may contain the filler composition in an amount of 1,000 parts by weight or more, 1,100 parts by weight or more, 1,200 parts by weight or more, 1,300 parts by weight or more, 1,400 parts by weight or more, 1,500 parts by weight or more, 1,600 parts by weight or more, or 1,700 parts by weight or more, relative to 100 parts by weight of the acrylic polymer component. In addition, in another example, the curable composition may contain the filler composition in an amount of 6,000 parts by weight or less, 5,750 parts by weight or less, 5,500 parts by weight or less, 5,250 parts by weight or less, 5,000 parts by weight or less, 4,750 parts by weight or less, 4,500 parts by weight or less, 4,250 parts by weight or less, or 4,000 parts by weight or less. The content ratio of the filler composition in the curable composition may be within a range formed by appropriately selecting the upper limit and the lower limit as listed above.
[0065] The curable composition according to one example of the present application may form a cured product ensuring thermal conductivity and insulation properties by including the filler composition within the content ratio, and may ensure appropriate fluidity to improve processability of the curable composition.
[0066] Relative to 100 parts by weight of acrylic polymer components, the curable composition according to an example of the present application can include acrylic monomer components in an amount of 70 parts by weight or more, 75 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 90 parts by weight or more, or 95 parts by weight or more. In addition, in another example, relative to 100 parts by weight of acrylic polymer components, the curable composition can include acrylic monomer components in an amount of 380 parts by weight or less, 340 parts by weight or less, 300 parts by weight or less, 280 parts by weight or less, 260 parts by weight or less, or 240 parts by weight or less. The content ratio of the acrylic monomer components in the curable composition can be in the scope formed by appropriately selecting the upper and lower limits listed above.
[0067] The curable composition according to one example of the present application may form a cured product having excellent hardness by including the acrylic monomer component within the content ratio.
[0068] Since one or more of the polymerized units selected from the acrylic polymer component and the acrylic monomer component contain a cyclic ether-based acrylic compound, the curable composition according to one example of the present application can exhibit rapid curability at room temperature even when containing a filler composition. In addition, even when the filler composition is contained in an excessive amount (70% by weight or more relative to the total weight), rapid curability can be ensured at room temperature and high humidity conditions.
[0069] The cyclic ether-based acrylic compound included in the curable composition according to one example of the present application may include a compound represented by the following Formula 2. In addition, the cyclic ether-based acrylic compound included in the curable composition may include one or two or more compounds represented by the following Formula 2.
[0070] [Formula 2]
[0071]
[0072] In Formula 2, R3 may be hydrogen or an alkyl group having 1 to 20 carbon atoms. L1 and L2 may each independently be a single bond or an alkylene group. L3 may be an alkylene group. In addition, L1 and L2 may each independently be a single bond or an alkylene group having 1 to 20 carbon atoms. In addition, L3 may be an alkylene group having 1 to 20 carbon atoms.
[0073] Preferably, L1 may be a single bond or a linear or branched alkylene group having 1 to 8 carbon atoms, and more preferably, L1 may be a linear or branched alkylene group having 1 to 4 carbon atoms.
[0074] In addition, preferably, L2 may be a single bond or a linear or branched alkylene group having 1 to 4 carbon atoms, and more preferably, L2 may be a single bond.
[0075] In addition, preferably, L3 may be a linear or branched alkylene group having 1 to 12 carbon atoms, and more preferably, L3 may be a linear or branched alkylene group having 1 to 8 carbon atoms, or a linear or branched alkylene group having 1 to 4 carbon atoms.
[0076] In addition, in Formula 2, the sum of the number of carbon atoms present in L2 and L3 may be in the range of 1 to 8. The sum of the number of carbon atoms may be 7 or less, 6 or less, 5 or less, 4 or less, or 3 or less, or may be 1 or more, 2 or more, or 3 or more. The sum of the number of carbon atoms in L2 and L3 is the number of carbon atoms of the alkylene group of L3 when L3 is an alkylene group and L2 is a single bond, and the sum of the number of carbon atoms of the alkylene group of L3 and the number of carbon atoms of the alkylene group of L2 when L3 is an alkylene group and L2 is also an alkylene group. In addition, when a substituent is present in the alkylene group, the number of carbon atoms present in the substituent is not included in the sum.
[0077] The compound represented by the above formula 2 is, for example, oxirane (meth)acrylate, oxetane (meth)acrylate, tetrahydrofuran (meth)acrylate, tetrahydro-2H-pyran (meth)acrylate, oxirane methyl (meth)acrylate (or glycidyl (meth)acrylate), oxetane ethyl (meth)acrylate and tetrahydrofuranyl methyl (meth)acrylate (or tetrahydrofurfuryl (meth)acrylate), and the like.
[0078] In addition, the cyclic ether-based acrylic compound included in the curable composition according to one example of the present application may include the compound represented by the above Formula 2 in an amount of 55 wt % or more, 60 wt % or more, 65 wt % or more, 70 wt % or more, 75 wt % or more, 80 wt % or more, 85 wt % or more, 90 wt % or more, 95 wt % or more, or 100 wt % relative to the total weight of the cyclic ether-based acrylic compound.
[0079] The curable composition according to an example of the present application may include a filler composition as described above. In the filler composition, its type, shape and size etc. are not particularly limited. In addition, the filler composition may include one or more filler particles. In addition, even if the same type of filler particles are used, the filler composition may also be a filler composition mixed with particles of different shapes, and may also be a filler composition mixed with particles of different particle average particle diameters. For example, the filler composition may be a filler composition mixed with aluminum hydroxide and aluminum oxide (aluminum oxide), wherein the shape and average particle diameter of aluminum hydroxide and aluminum oxide may be different from each other.
[0080] The filler composition included in the curable composition according to one example of the present application may include filler particles with an average particle size of 70 μm or more. In another example, the average particle size of the filler particles may be 75 μm or more, 80 μm or more, 85 μm or more, 90 μm or more, 95 μm or more, 100 μm or more, 105 μm or more, 110 μm or more, 115 μm or more, or 120 μm or more, or may have a size greater than those. Filler particles with an average particle size within the above range may be referred to as A filler particles in the present application, wherein the A filler particles are not particularly limited in type and quantity, as long as the average particle size is 70 μm or more.
[0081] The term average particle size of filler particles as used herein is the so-called D50 particle size (median particle size), which may mean a particle size at 50% accumulation based on volume of particle size distribution. That is, the particle size at a point where the cumulative value on a cumulative curve where the particle size distribution is obtained based on volume and the total volume is 100% becomes 50% may be regarded as the average particle size. Such a D50 particle size may be measured by a laser diffraction method.
[0082] The shape of the filler particles having an average particle diameter of 70 μm or more may be appropriately selected from spherical shapes and / or non-spherical shapes (eg, needle-like and plate-like shapes) as required and used, but is not limited thereto.
[0083] As used herein, the term "spherical shape" of filler particles may mean a sphericity of about 0.9 or more, and "non-spherical shape" may mean a sphericity of less than about 0.9.
[0084] Sphericity can be determined by particle shape analysis of fillers. Specifically, the sphericity of fillers that are three-dimensional particles can be defined as the ratio (S' / S) of the surface area (S') of a sphere having the same volume as the volume of the particle to the surface area (S) of the particle. For actual particles, circularity is generally used. Circularity is expressed as the ratio of the boundary (A) of a circle having the same image and the same area as the two-dimensional image of the actual particles thus obtained to the boundary (P) of the image, which is obtained by the following equation.
[0085] <Circularity equation>
[0086] Circularity = 4πA / P 2
[0087] The circularity is expressed as a value from 0 to 1, wherein a perfect circle has a value of 1, and when the particle has an irregular shape, it has a value less than 1. The sphericity value in the present application can be measured as the average value of circularity measured with Marvern's particle shape analysis equipment (FPIA-3000).
[0088] Relative to the gross weight of filler composition, the filler composition included in the curable composition according to an example of the present application can include filler particles with an average particle size of 70 μm or more with 10 wt % or more, 15 wt % or more, 20 wt % or more, 25 wt % or more, 30 wt % or more, or 35 wt % or more. In addition, in another example, the filler composition can include filler particles with an average particle size of 70 μm or more with 100 wt % or less, 99.5 wt % or less, 90 wt % or less, 80 wt % or less, 70 wt % or less, 60 wt % or less, 50 wt % or less, or 40 wt % or less. Filler particles with an average particle size of 70 μm or more can be included in the scope formed by appropriately selecting the upper and lower limits listed above.
[0089] The filler composition included in the curable composition according to one example of the present application may include filler particles having an average particle size of 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, or 50 μm or more. In addition, in another example, the filler composition may include filler particles having an average particle size of less than 70 μm, 65 μm or less, 60 μm or less, 55 μm or less, or 50 μm or less. Filler particles with an average particle size within the above range may be referred to as B filler particles in the present application. B filler particles are not particularly limited in type and quantity as long as the average particle size satisfies the above range.
[0090] The filler composition included in the curable composition according to one example of the present application may contain the B filler particles in an amount of 5 wt % or more, 10 wt % or more, 15 wt % or more, or 20 wt % or more relative to the total weight of the filler composition, and in another example, it may contain the B filler particles in an amount of 100 wt % or less, 90 wt % or less, 80 wt % or less, 70 wt % or less, 60 wt % or less, 50 wt % or less, 40 wt % or less, or 30 wt % or less. The B filler particles may be contained within the range formed by appropriately selecting the upper and lower limits listed above.
[0091] In addition, the filler composition included in the curable composition according to one example of the present application may include A filler particles and B filler particles.
[0092] When the filler composition included in the curable composition according to one example of the present application includes A filler particles and B filler particles, the curable composition may include B filler particles in an amount of 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more relative to 100 parts by weight of A filler particles. In addition, in another example, the curable composition may include B filler particles in an amount of 200 parts by weight or less, 180 parts by weight or less, 160 parts by weight or less, 140 parts by weight or less, 120 parts by weight or less, 100 parts by weight or less, or 80 parts by weight or less relative to 100 parts by weight of A filler particles. In addition, if the content ratio of the A filler particles and the B filler particles in the filler composition is adjusted to be within the above range, a curable composition with an appropriate viscosity can be formed, and a cured product with excellent thermal conductivity can be formed.
[0093] When the filler composition included in the curable composition according to one example of the present application includes A filler particles and B filler particles, the diameter (D A ) and the diameter of filler particle B (D B ) ratio (D A / D B ) can be 1.05 or greater, 1.1 or greater, 1.15 or greater, 1.2 or greater, 1.25 or greater, 1.3 or greater, 1.35 or greater, or 1.4 or greater, and in another example, the ratio (D A / D B ) can be 2.3 or less, 2.25 or less, 2.2 or less, 2.15 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, or 1.4 or less. The diameter (D) of the filler particle A can be 2.3 or less, 2.25 or less, 2.2 or less, 2.15 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, or 1.4 or less. A ) and the diameter of filler particle B (D B ) ratio (D A / D B ) may be included in the range formed by appropriately selecting the upper and lower limits as listed above. In addition, when the diameter (D A ) and the diameter of filler particle B (D B ) ratio (D A / D B ) satisfies the above range, rapid curability of the curable composition can be ensured.
[0094] The filler composition included in the curable composition according to one example of the present application may include filler particles having an average particle size of less than 20 μm, 17.5 μm or less, 15 μm or less, 12.5 μm or less, 10 μm or less, 7.5 μm or less, 5 μm or less, 2.5 μm or less, or 1 μm or less. In another example, the filler composition may include filler particles having an average particle size of 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.2 μm or more, 0.4 μm or more, 0.8 μm or more, or 1 μm or more. Filler particles with an average particle size within the above range may be referred to as C filler particles in the present application. C filler particles are not particularly limited in type and quantity as long as the average particle size satisfies the above range.
[0095] The filler composition included in the curable composition according to one example of the present application may include one or more selected from A filler particles, B filler particles, and C filler particles. In addition, the filler composition included in the curable composition according to one example of the present application may include one or more selected from A filler particles, B filler particles, and C filler particles.
[0096] When the filler composition included in the curable composition according to one example of the present application includes A filler particles and C filler particles, relative to 100 parts by weight of the A filler particles, the curable composition can include the C filler particles in an amount of 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 100 parts by weight or more. In addition, in another example, relative to 100 parts by weight of the A filler particles, the curable composition can include the C filler particles in an amount of 300 parts by weight or less, 280 parts by weight or less, 260 parts by weight or less, 240 parts by weight or less, 220 parts by weight or less, or 200 parts by weight or less. Relative to 100 parts by weight of the A filler particles, the C filler particles can be included in the range formed by appropriately selecting the upper and lower limits listed above.
[0097] When the filler composition included in the curable composition according to one example of the present application includes A filler particles and C filler particles, the diameter (D A ) and the diameter of the C filler particles (D C ) ratio (D A / D C ) can be 2.5 or more, 4 or more, 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, 35 or more, or 40 or more, and in another example, the ratio (D A / DC ) can be 20,000 or less, 10,000 or less, 5,000 or less, 2,000 or less, 1,000 or less, 500 or less, 100 or less, 80 or less, 60 or less, 50 or less, or 45 or less. The diameter (D) of the filler particle A may be 20,000 or less, 10,000 or less, 5,000 or less, 2,000 or less, 1,000 or less, 500 or less, 100 or less, 80 or less, 60 or less, 50 or less, or 45 or less. A ) and the diameter of the C filler particles (D C ) ratio (D A / D C ) may be included in the range formed by appropriately selecting the upper and lower limits listed above. In addition, when the diameter (D A ) and the diameter of the C filler particles (D C ) ratio (D A / D C ) satisfies the above range, rapid curability of the curable composition can be ensured.
[0098] When the curable composition according to one example of the present application includes the filler composition in the above content ratio or satisfies the above diameter ratio according to the average particle size, excellent thermal conductivity of the cured product and rapid curability of the curable composition may be ensured.
[0099] The filler composition included in the curable composition according to one example of the present application can be a thermally conductive filler composition for processing heat generated by a battery, etc., and can include at least one or more thermally conductive filler particles. In the thermally conductive filler particles, the thermal conductivity of the thermally conductive filler particles themselves can be about 1W / mK or greater, 5W / mK or greater, 10W / mK or greater, or 15W / mK or greater, and in another example, it can be about 400W / mK or less, about 350W / mK or less, or about 300W / mK or less. The thermal conductivity of the thermally conductive filler particles that can be included in the filler composition is not particularly limited, but can be a value measured according to ASTM E1461.
[0100] The type of thermally conductive filler particles contained in the filler composition is not particularly limited as long as the thermal conductivity itself satisfies the above range, but it can be, for example, an oxide, such as aluminum oxide (aluminum oxide), magnesium oxide, beryllium oxide or titanium oxide; a nitride, such as boron nitride, silicon nitride or aluminum nitride; a carbide, such as silicon carbide; a hydrated metal, such as aluminum hydroxide or magnesium hydroxide; a metal filler, such as copper, silver, iron, aluminum or nickel; a metal alloy filler, such as titanium; or a mixture thereof; and the like.
[0101] The filler composition included in the curable composition according to one example of the present application may include filler particles having a Mohs hardness of 6 or greater, 6.5 or greater, 7 or greater, 7.5 or greater, 8 or greater, or 8.5 or greater. The term Mohs hardness as used herein can be measured using a Mohs durometer. In addition, filler particles having a Mohs hardness within the above range may be referred to as first filler particles in the present application.
[0102] The first filler particles may be included in an amount of 30 wt % or more, 35 wt % or more, 40 wt % or more, 45 wt % or more, 50 wt % or more, 55 wt % or more, 60 wt % or more, 65 wt % or more, 70 wt % or more, 75 wt % or more, 80 wt % or more, 85 wt % or more, or 90 wt % or more, relative to the total weight of the filler composition, and in another example, it may be included in an amount of 100 wt % or less, 97.5 wt % or less, 95 wt % or less, or 92.5 wt % or less, relative to the total weight of the filler composition. The first filler particles may be included within a range formed by appropriately selecting the upper and lower limits listed above.
[0103] In addition, in the filler composition included in the curable composition according to one example of the present application, the filler particles having an average particle diameter of 70 μm or more (i.e., the above-mentioned A filler particles) may include filler particles having a Mohs hardness of 6 or more, 6.5 or more, 7 or more, 7.5 or more, 8 or more, or 8.5 or more (i.e., the above-mentioned first filler particles). At this time, the A filler particles may include the first filler particles in an amount of 55% by weight or more, 75% by weight or more, or 95% by weight or more relative to the total weight of the A filler particles.
[0104] In addition, in the filler composition included in the curable composition according to one example of the present application, the filler particles having an average particle size of less than 20 μm (i.e., the above-mentioned C filler particles) may also include filler particles having a Mohs hardness of 6 or more, 6.5 or more, 7 or more, 7.5 or more, 8 or more, or 8.5 or more. In this case, the C filler particles may include the first filler particles in an amount of 55 wt % or more, 75 wt % or more, or 95 wt % or more relative to the total weight of the C filler particles.
[0105] In addition, the filler composition included in the curable composition may also include filler particles having a Mohs hardness of less than 6, 5.5 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, or 3 or less to adjust the viscosity, workability and hardness of the curable composition after curing. Filler particles having a Mohs hardness within the above range may be referred to as second filler particles in the present application.
[0106] The second filler particles may be included in an amount of 50 parts by weight or less, 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, 30 parts by weight or less, or 25 parts by weight or less, relative to 100 parts by weight of the first filler particles. In another example, the second filler particles may be included in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 1 part by weight or more, or 5 parts by weight or more, relative to 100 parts by weight of the first filler particles. The second filler particles may be included in a range formed by appropriately selecting the upper and lower limits listed above, relative to 100 parts by weight of the first filler particles.
[0107] In addition, in the filler composition included in the curable composition according to one example of the present application, the filler particles having an average particle size of more than 20 μm to less than 70 μm (i.e., the above-mentioned B filler particles) may include filler particles having a Mohs hardness of less than 6, 5.5 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, or 3 or less (i.e., the above-mentioned second filler particles). In addition, the B filler particles may also include filler particles having a Mohs hardness of 6 or more, 6.5 or more, 7 or more, 7.5 or more, 8 or more, or 8.5 or more (i.e., the above-mentioned first filler particles). At this time, the B filler particles may include the second filler particles in an amount of 55% by weight or more, 75% by weight or more, or 95% by weight or more relative to the total weight of the B filler particles.
[0108] The curable composition according to one example of the present application may include an acrylic monomer component as described above.
[0109] The acrylic monomer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound as described above. In addition, the cyclic ether-based acrylic compound included in the acrylic monomer component may include one or two or more compounds represented by Formula 2 below.
[0110] [Formula 2]
[0111]
[0112] Since the content of the above formula 2 is the same as above, the details will be omitted.
[0113] Relative to the gross weight of acrylic acid monomer component, the acrylic acid monomer component of the curable composition according to an example of the present application can include an acrylic acid compound based on cyclic ethers in an amount of 60 wt % or more, 65 wt % or more, 70 wt % or more, 75 wt % or more, 80 wt % or more, or 85 wt % or more. In another example, relative to the gross weight of acrylic acid monomer component, the acrylic acid monomer component of the curable composition can include an acrylic acid compound based on cyclic ethers in an amount of 95 wt % or less, 92.5 wt % or less, 90 wt % or less, or 87.5 wt % or less. The content range of the acrylic acid compound based on cyclic ethers in the acrylic acid monomer component can be included in the range formed by appropriately selecting the upper and lower limits listed above. In addition, when the content range of the acrylic acid compound based on cyclic ethers in the acrylic acid monomer component satisfies the above range, the room temperature rapid curability of the curable composition can be ensured, wherein even in the state of having excessive filler, the room temperature rapid curability can be ensured, and the cured product of the curable composition can be made to have excellent adhesion.
[0114] The acrylic monomer component of the curable composition according to an example of the present application may not substantially contain aromatic compounds. The aromatic compound may be an aromatic compound including aryl (meth)acrylate, in particular, may be a (meth)acrylate having a phenolic group, etc. For example, the aromatic compound may be exemplified by phenyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, phenol ethylene oxide-modified acrylate, p-cumyl ethylene oxide-modified acrylate, and nonylphenol ethylene oxide-modified acrylate, etc., but is not limited thereto.
[0115] The curable composition according to one example of the present application substantially does not include an aromatic compound, and thus a yellowing phenomenon may be suppressed even if a cured product of the curable composition is exposed to heat for a long period of time.
[0116] The term “substantially not included” as used herein may mean that it is included in an amount of 10 wt % or less, 9 wt % or less, 8 wt % or less, 7 wt % or less, 6 wt % or less, 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.5 wt % or less, 0.1 wt % or less, 0.05 wt % or less, 0.01 wt % or less, 0.005 wt % or less, 0.001 wt % or less, 0.0005 wt % or less, or 0.0001 wt % or less, relative to the total weight of the curable composition, or theoretically 0 wt % in which it is not included at all.
[0117] The acrylic monomer component of the curable composition according to an example of the present application may include a hydroxyl-containing acrylic compound. When the acrylic monomer component includes a hydroxyl-containing acrylic compound, the cured product of the curable composition can be made to have an appropriate hardness so that it is not brittle and has flexibility. At this time, appropriate hardness can mean that the cured product is not evaluated as brittle to the extent that it will be described in detail below. In addition, when the acrylic monomer component of the curable composition according to an example of the present application uses a hydroxyl-containing acrylic compound and a cyclic ether-based acrylic compound at the same time, a curable composition with more excellent thermal conductivity can be provided.
[0118] The hydroxyl-containing acrylic compound that may be included in the acrylic monomer component according to one example of the present application may include a compound represented by the following Formula 3. In addition, the hydroxyl-containing acrylic compound that may be included in the acrylic monomer component may include one or two or more compounds represented by the following Formula 3.
[0119] [Formula 3]
[0120]
[0121] In the above formula 3, R4 may be hydrogen or an alkyl group having 1 to 20 carbon atoms. In addition, L4 may be one selected from the group consisting of an alkylene group having 1 to 20 carbon atoms, an alkenylene group having 2 to 20 carbon atoms, an alkynylene group having 2 to 20 carbon atoms, an arylene group having 6 to 30 carbon atoms, and a heteroarylene group having 5 to 30 ring atoms.
[0122] Preferably, L4 may be a linear or branched alkylene group having 1 to 8 carbon atoms, and more preferably, L4 may be a linear or branched alkylene group having 1 to 4 carbon atoms.
[0123] In addition, L4 may be further substituted with a hydroxyl group.
[0124] Examples of the compound represented by the above formula 3 include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate (glyceryl mono(meth)acrylate), glyceryl poly(meth)acrylate, 2,2-dihydroxyethyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate.
[0125] In addition, the hydroxyl-containing acrylic compound that may be included in the acrylic monomer component according to one example of the present application may include the compound represented by the above Formula 3 in an amount of 55 wt % or more, 60 wt % or more, 65 wt % or more, 70 wt % or more, 75 wt % or more, 80 wt % or more, 85 wt % or more, 90 wt % or more, 95 wt % or more, or 100 wt % relative to the total weight of the hydroxyl-containing acrylic compound.
[0126] The acrylic monomer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound and a hydroxyl-containing acrylic compound.
[0127] Relative to 100 parts by weight of cyclic ether-based acrylic compounds, the acrylic monomer component of the curable composition according to an example of the present application can include hydroxyl-containing acrylic compounds in an amount of 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, 9 parts by weight or more, or 11 parts by weight or more. In another example, relative to 100 parts by weight of cyclic ether-based acrylic compounds, the acrylic monomer component of the curable composition can include hydroxyl-containing acrylic compounds in an amount of 18 parts by weight or less, 17.5 parts by weight or less, 17 parts by weight or less, 16.5 parts by weight or less, or 16 parts by weight or less. The content range of the hydroxyl-containing acrylic compound in the acrylic monomer component can be included in the range formed by appropriately selecting the upper and lower limits listed above. In addition, when the content range of the hydroxyl-containing acrylic compound in the acrylic monomer component meets the above range, a cured product with appropriate hardness can be obtained, and the curable composition can be made flexible without brittleness even after it is cured.
[0128] In addition, the hydroxyl-containing acrylic compound that can be included in the acrylic monomer component according to one example of the present application can have a thermal conductivity of 0.15 W / mK or more, 0.2 W / mK or more, 0.25 W / mK or more, or 0.3 W / mK or more. By using a hydroxyl-containing acrylic compound whose thermal conductivity satisfies the above range, the cured product of the curable composition can have an excellent heat dissipation effect.
[0129] Here, the self thermal conductivity of the hydroxyl-containing acrylic compound is a value obtained by measuring the thermal conductivity of a cured product of the hydroxyl-containing acrylic compound measured using a hot plate. Specifically, in a state where the hydroxyl-containing acrylic compound is produced as a disc-shaped sample (cured product) having a diameter of 4 cm and a thickness of 500 μm, the thermal conductivity of the cured product of the hydroxyl-containing acrylic compound is measured along the thickness direction of the sample according to ISO 22007-2 standard.
[0130] The acrylic monomer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound and acrylamide.
[0131] In addition, the acrylic monomer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound, a hydroxyl-containing acrylic compound, and acrylamide.
[0132] Relative to 100 parts by weight of acrylic acid compounds based on cyclic ethers, the acrylic acid monomer component of the curable composition according to an example of the present application can include acrylamide in an amount of 1 part by weight or more, 1.1 parts by weight or more, 1.2 parts by weight or more, 1.3 parts by weight or more, 1.4 parts by weight or more, or 1.5 parts by weight or more. In another example, relative to 100 parts by weight of acrylic acid compounds based on cyclic ethers, the acrylic acid monomer component of the curable composition can include acrylamide in an amount of 5 parts by weight or less, 4.5 parts by weight or less, 4 parts by weight or less, 3.5 parts by weight or less, 3 parts by weight or less, or 2.5 parts by weight or less. The content range of acrylamide in the acrylic acid monomer component can be included in the range formed by appropriately selecting the upper and lower limits listed above. In addition, when the content range of acrylamide in the acrylic acid monomer component meets the above range, the cured product of the curable composition can be made to have improved stability, impact resistance and vibration resistance.
[0133] If necessary, in addition to the cyclic ether-based acrylic compound, hydroxyl-containing acrylic compound and acrylamide as described above, the acrylic monomer component of the curable composition according to one example of the present application may further include another acrylic compound. The other acrylic compound may be a compound other than the cyclic ether-based acrylic compound, hydroxyl-containing acrylic compound and acrylamide in the compound represented by the above formula 1.
[0134] As described above, the curable composition according to one example of the present application may include an acrylic polymer component. The acrylic polymer component may include one or more polymerization units.
[0135] As described above, the polymerization unit of the acrylic polymer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound. In addition, the cyclic ether-based acrylic compound included in the polymerization unit of the acrylic polymer component may include one or two or more compounds represented by the following formula 2.
[0136] [Formula 2]
[0137]
[0138] Since the content of the above formula 2 is the same as above, the details will be omitted.
[0139] Relative to gross weight, the polymerization unit of the acrylic polymer component of the curable composition of an example of the present application can include an acrylic compound based on cyclic ethers in an amount of 70 wt % or more, 75 wt % or more, 80 wt % or more, 85 wt % or more, or 90 wt % or more. In another example, relative to gross weight, the polymerization unit of the acrylic polymer component of the curable composition can include an acrylic compound based on cyclic ethers in an amount of 99 wt % or less, 97.5 wt % or less, 95 wt % or less, or 92.5 wt % or less. The content range of the acrylic compound based on cyclic ethers in the polymerization unit of the acrylic polymer component can be included in the range formed by appropriately selecting the upper and lower limits listed above. In addition, when the content range of the acrylic compound based on cyclic ethers in the polymerization unit of the acrylic polymer component satisfies the above range, the room temperature rapid curability of the curable composition can be ensured, wherein even in the state of the presence of excessive filler, the room temperature rapid curability can be ensured, and the cured product of the curable composition can be made to have excellent adhesion.
[0140] The polymerization unit of the acrylic polymer component of the curable composition according to an example of the present application may not contain aromatic compounds substantially.Aromatic compounds may be aromatic compounds including (meth) aryl acrylate, particularly, (meth) acrylates with phenolic groups, etc. For example, aromatic compounds may be exemplified as phenyl (meth) acrylate, (meth) acrylate 2-hydroxy-3-phenoxypropyl, phenol ethylene oxide-modified acrylate, p-cumyl ethylene oxide-modified acrylate and nonylphenol ethylene oxide-modified acrylate, etc., but are not limited thereto. Here, the meaning that it does not contain substantially is the same as defined above. The polymerization unit of the acrylic polymer component does not contain aromatic compounds substantially, so that even if the cured product of the curable composition is exposed to heat for a long time, the yellowing phenomenon can be suppressed.
[0141] The polymerization unit of the acrylic polymer component of the curable composition according to an example of the present application may contain a hydroxyl-containing acrylic compound. When the polymerization unit of the acrylic polymer component contains a hydroxyl-containing acrylic compound, the cured product of the curable composition can have an appropriate hardness so that it is not brittle and has flexibility. In addition, when the polymerization unit of the acrylic polymer component of the curable composition according to an example of the present application uses a hydroxyl-containing acrylic compound and a cyclic ether-based acrylic compound at the same time, a curable composition with more excellent thermal conductivity can be provided.
[0142] The hydroxyl-containing acrylic compound contained in the polymerization unit of the acrylic polymer component of the curable composition according to one example of the present application may include a compound represented by the following Formula 3. In addition, the hydroxyl-containing acrylic compound that may be contained in the polymerization unit of the acrylic polymer component may include one or two or more compounds represented by the following Formula 3.
[0143] [Formula 3]
[0144]
[0145] Since the content of the above formula 3 is the same as above, the details will be omitted.
[0146] The polymerization unit of the acrylic polymer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound and a hydroxyl-containing acrylic compound.
[0147] The polymerization unit of the acrylic polymer component of the curable composition according to one example of the present application may include the hydroxyl-containing acrylic compound in an amount of 0.1 parts by weight or more, 0.25 parts by weight or more, 0.5 parts by weight or more, 0.75 parts by weight or more, 1 part by weight or more, 1.25 parts by weight or more, 1.5 parts by weight or more, 1.75 parts by weight or more, 2 parts by weight or more, 2.25 parts by weight or more, 2.5 parts by weight or more, 2.75 parts by weight or more, 3 parts by weight or more, or 3.25 parts by weight or more, relative to 100 parts by weight of the cyclic ether-based acrylic compound. In another example, the polymerization unit of the acrylic polymer component of the curable composition may include the hydroxyl-containing acrylic compound in an amount of 10 parts by weight or less, 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, or 4 parts by weight or less. The content range of the hydroxyl-containing acrylic compound in the polymerization unit of the acrylic polymer component may be included in the range formed by appropriately selecting the upper and lower limits as listed above. In addition, when the content range of the hydroxyl-containing acrylic compound in the polymerization unit of the acrylic polymer component satisfies the above range, a cured product having an appropriate hardness can be obtained, and the curable composition can be made flexible without brittleness even after it is cured.
[0148] In addition, the hydroxyl-containing acrylic compound that may be included in the polymerization unit of the acrylic polymer component according to an example of the present application may have a thermal conductivity of 0.15 W / mK or more, 0.2 W / mK or more, 0.25 W / mK or more, or 0.3 W / mK or more. By using a hydroxyl-containing acrylic compound whose thermal conductivity satisfies the above range, the cured product of the curable composition can have an excellent heat dissipation effect. The thermal conductivity of the hydroxyl-containing acrylic compound can be measured using the hot plate method as described above.
[0149] The polymerization unit of the acrylic polymer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound and acrylamide.
[0150] In addition, the polymerization unit of the acrylic polymer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound, a hydroxyl-containing acrylic compound, and acrylamide.
[0151] The polymerization units of the acrylic polymer component of the curable composition according to one example of the present application may contain acrylamide in an amount of 1 part by weight or more, 1.5 parts by weight or more, 2 parts by weight or more, 2.5 parts by weight or more, 3 parts by weight or more, 3.5 parts by weight or more, 4 parts by weight or more, 4.5 parts by weight or more, 5 parts by weight or more, 5.5 parts by weight or more, 6 parts by weight or more, or 6.5 parts by weight or more, relative to 100 parts by weight of the cyclic ether-based acrylic compound. In another example, the polymerization units of the acrylic polymer component of the curable composition may contain acrylamide in an amount of 30 parts by weight or less, 28 parts by weight or less, 26 parts by weight or less, 24 parts by weight or less, 22 parts by weight or less, 20 parts by weight or less, 18 parts by weight or less, 16 parts by weight or less, 14 parts by weight or less, 12 parts by weight or less, 10 parts by weight or less, or 8 parts by weight or less. The content range of acrylamide in the polymerization unit of the acrylic polymer component can be included in the range formed by appropriately selecting the upper and lower limits listed above. In addition, when the content range of acrylamide in the polymerization unit of the acrylic polymer component satisfies the above range, the cured product of the curable composition can have improved stability, impact resistance and vibration resistance.
[0152] If necessary, in addition to the cyclic ether-based acrylic compound, hydroxyl-containing acrylic compound and acrylamide as described above, the polymerization unit of the acrylic polymer component of the curable composition according to one example of the present application may further include another acrylic compound. The other acrylic compound may be a compound other than the cyclic ether-based acrylic compound, hydroxyl-containing acrylic compound and acrylamide in the compound represented by the above formula 1.
[0153] The acrylic polymer component of the curable composition according to one example of the present application may be formed of an acrylic polymer precursor composition, and the polymerization units of the acrylic polymer component may be determined according to chemical substances included in the acrylic polymer precursor composition.
[0154] The acrylic polymer precursor composition forming the acrylic polymer component of the curable composition according to one example of the present application may include a cyclic ether-based acrylic compound, wherein the type and content of the cyclic ether-based acrylic compound that may be included in the polymerization unit of the acrylic polymer component as described above are the same, and therefore they will be omitted.
[0155] In addition, the acrylic polymer precursor composition forming the acrylic polymer component of the curable composition according to one example of the present application may include a hydroxyl-containing acrylic compound, wherein the type and content of the hydroxyl-containing acrylic compound that may be included in the polymerization unit of the acrylic polymer component as described above are the same, and therefore they will be omitted.
[0156] In addition, the acrylic polymer precursor composition forming the acrylic polymer component of the curable composition according to one example of the present application may contain acrylamide, wherein the content of acrylamide that may be contained in the polymerization unit of the acrylic polymer component as described above is the same, and thus they will be omitted.
[0157] The acrylic polymer component of the curable composition according to one example of the present application can be formed by adding a polymerization initiator to an acrylic polymer precursor composition and then initiating polymerization. The acrylic polymer precursor composition may further include a molecular weight regulator.
[0158] The acrylic polymer component of the curable composition according to an example of the present application can be formed by the polymerization reaction of an acrylic polymer precursor composition to which a polymerization initiator is added. The polymerization temperature of the polymerization reaction can be 55°C or higher, 56°C or higher, 57°C or higher, 58°C or higher, 59°C or higher, or 60°C or higher, and not more than about 70°C. In addition, as a polymerization initiator, a peroxide compound, an azo compound or a redox agent can be used, and a suitable polymerization initiator can be selected in consideration of the polymerization temperature. For example, the polymerization initiator is not particularly limited as long as it is used in the art, but 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) or a combination thereof can be used.
[0159] The acrylic polymer precursor composition of the acrylic polymer component of the curable composition according to one example of the present application may contain a polymerization initiator in an amount of 0.0001 wt % or more, 0.0005 wt % or more, 0.001 wt % or more, 0.0025 wt % or more, 0.005 wt % or more, 0.0075 wt % or more, or 0.01 wt % relative to the total weight of the acrylic polymer precursor composition. In another example, the acrylic polymer precursor composition may contain a polymerization initiator in an amount of 0.1 wt % or less, 0.075 wt % or less, 0.05 wt % or less, 0.025 wt % or less, or 0.02 wt % or less relative to the total weight of the acrylic polymer precursor composition. The content ratio of the polymerization initiator contained in the acrylic polymer precursor composition may be included in the range formed by appropriately selecting the upper and lower limits listed above. When the content ratio of the polymerization initiator contained in the acrylic polymer precursor composition satisfies the above range, the acrylic polymer component may be formed while maintaining polymerization stability and easily controlling the reaction.
[0160] In addition, in order to ensure polymerization stability when the acrylic polymer component is formed by polymerizing the acrylic polymer precursor composition, the polymerization initiator may be included in the acrylic polymer precursor composition in three or more times, four or more times, or five or more times. For example, when the polymerization initiator is introduced four times in an amount of about 0.02 wt % relative to the total weight of the acrylic polymer precursor composition, 0.005 wt % in an amount corresponding to 1 / 4 may be included in the acrylic polymer precursor composition before initiating the polymerization, and after initiating the polymerization to form some cross-linked structures, the polymerization reaction may be completed by introducing 0.005 wt % in an amount corresponding to 1 / 4 three times and then further polymerizing it. When the polymerization initiator is introduced once and polymerized, or is divided into two portions and introduced, the target conversion rate must be achieved once or twice, so that an excessive amount of the polymerization initiator must be introduced, and thus it may be difficult to control the reaction.
[0161] The acrylic polymer component of the curable composition according to one example of the present application may be formed by polymerization of an acrylic polymer precursor composition including a molecular weight regulator in addition to a polymerization initiator to achieve a desired molecular weight.
[0162] The molecular weight regulator is not particularly limited as long as it can be used in the art, but includes, for example, alkyl mercaptan, such as n-octyl mercaptan, n-dodecyl mercaptan, tert-dodecyl mercaptan, 1,4-butanedithiol, 1,6-hexanedithiol, ethylene glycol dithiopropionate, butanediol dithioglycolate, butanediol dithiopropionate, hexanediol dithioglycolate, hexanediol dithiopropionate, trimethylolpropane tris-(β-thiopropionate), and pentaerythritol tetrathiopropionate; α-methylstyrene dimer; terpinolene; etc. In view of the availability of the molecular weight regulator, it is preferred to use alkyl mercaptan, and one thereof or a combination of two or more thereof may also be used.
[0163] The acrylic polymer precursor composition of the acrylic polymer component of the curable composition according to one example of the present application may contain a molecular weight regulator in an amount of 0.1 wt % or more, 0.5 wt % or more, 1 wt % or more, 2 wt % or more, 3 wt % or more, 4 wt % or more, or 5 wt % or more relative to the total weight of the acrylic polymer precursor composition. In another example, the acrylic polymer precursor composition may contain a molecular weight regulator in an amount of 10 wt % or less, 9 wt % or less, 8 wt % or less, 7 wt % or less, or 6 wt % or less relative to the total weight of the acrylic polymer precursor composition. The content ratio of the molecular weight regulator contained in the acrylic polymer precursor composition may be included in the range formed by appropriately selecting the upper and lower limits listed above. When the content ratio of the molecular weight regulator contained in the acrylic polymer precursor composition satisfies the above range, an acrylic polymer component with a suitable number average molecular weight and / or weight average molecular weight may be formed.
[0164] In the acrylic polymer component of the curable composition according to one example of the present application, the glass transition temperature (T g ) can be -50°C or higher, -48°C or higher, -46°C or higher, -44°C or higher, -42°C or higher, or -40°C or higher, and in another example, it can be 0°C or lower, -2°C or lower, -4°C or lower, -6°C or lower, -8°C or lower, or -10°C or lower.
[0165] In the acrylic polymer component of the curable composition according to one example of the present application, the viscosity measured at room temperature may be 1,000 cP or more, 1,200 cP or more, 1,400 cP or more, 1,600 cP or more, or 1,800 cP or more, and in another example, the viscosity may be 6,000 cP or less, 5,900 cP or less, 5,800 cP or less, 5,700 cP or less, 5,600 cP or less, or 5,500 cP or less. The viscosity of the acrylic polymer component may be a value measured at about 25° C. and 15 rpm using a viscometer (manufacturer: Brookfield, model name: Brookfield AMETEK / DV3T) and a shaft 63 according to the method for measuring viscosity as described above.
[0166] The weight average molecular weight (M) of the acrylic polymer component of the curable composition according to one example of the present application measured using GPC (gel permeation chromatography) is W ) may be 1,000 g / mol or more, 2,000 g / mol or more, 3,000 g / mol or more, 4,000 g / mol or more, 5,000 g / mol or more, 6,000 g / mol or more, or 7,000 g / mol or more, and in another example, the weight average molecular weight (M) of the acrylic polymer component measured using GPC (gel permeation chromatography) is W ) may be 14,500 g / mol or less, 14,250 g / mol or less, 14,000 g / mol or less, 13,750 g / mol or less, 13,500 g / mol or less, 13,250 g / mol or less, or 13,000 g / mol or less. The weight average molecular weight (M) of the acrylic polymer component measured using GPC (gel permeation chromatography) W ) may be included in the range formed by appropriately selecting the upper and lower limits as listed above. When the weight average molecular weight (M) of the acrylic polymer component is measured using GPC (gel permeation chromatography), W ) satisfies the above range, an appropriate curing rate of the curable composition can be ensured, and miscibility with a filler (particularly, an excess filler) in the curable composition can be ensured.
[0167] If necessary, the curable composition according to one example of the present application may further include a peroxide compound. The peroxide compound may be a material that initiates a polymerization reaction of the curable composition.
[0168] The peroxide compound may include, for example, ketone peroxide compounds such as methyl ethyl ketone peroxide (MEKP), cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, methylcyclohexanone peroxide, methyl acetoacetate peroxide, and acetylacetone peroxide; hydroperoxide compounds such as tert-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroxide, p-methane hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, and 1,1,3,3-tetramethylbutyl hydroperoxide; diacyl peroxide compounds such as acetyl peroxide, isobutyl peroxide, octanoyl peroxide, decanoyl peroxide, lauroyl peroxide, 3,3,5-trimethylhexanoyl peroxide, succinic acid peroxide, benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, and methyl-toluoyl peroxide; acyl peroxide compounds such as benzoyl peroxide (benzoyl hydroperoxide, benzoyl hydroperoxide, 2,4-dichlorobenzoyl peroxide, and methyl-toluoyl peroxide; peroxide, BPO), but not limited thereto. In addition, one or two or more of the peroxide compounds may be used.
[0169] Relative to the acrylic polymer component of 100 weight portions, can comprise peroxide compound with 1 weight portion or more, 2 weight portions or more, 3 weight portions or more, 4 weight portions or more, 5 weight portions or more or 6 weight portions or more amount according to the curable composition of an example of the application.In another example, relative to the acrylic polymer component of 100 weight portions, curable composition can comprise peroxide compound with 10 weight portions or less, 9 weight portions or less, 8 weight portions or less or 7 weight portions or less amount.The content ratio of the peroxide compound comprising in the curable composition can be included in the scope formed by suitably selecting the upper and lower limits listed as above.When the content ratio of the peroxide compound comprising in the curable composition satisfies above scope, can form the curable composition that has guaranteed enough curability and storage stability, and can form the cured product that has guaranteed suitable bonding force.
[0170] If necessary, the curable composition according to one example of the present application may further include a metal catalyst.
[0171] As the metal catalyst, an organic acid metal salt or an organic metal chelate can be used. The organic acid metal salt or the organic metal chelate can be, for example, a metal naphthalene dicarboxylic acid, such as cobalt naphthalene dicarboxylic acid, copper naphthalene dicarboxylic acid, and manganese naphthalene dicarboxylic acid; a metal octenoic acid, such as cobalt octenoic acid, copper octenoic acid, and manganese octenoic acid; a metal acetoacetate, such as copper acetoacetate, titanium acetoacetate, manganese acetoacetate, chromium acetoacetate, iron acetoacetate, vanadium acetoacetate, and cobalt acetoacetate, etc. In addition, one or two or more of the metal catalysts can be used.
[0172] Relative to the acrylic polymer component of 100 weight parts, the curable composition according to an example of the present application can include a metal catalyst with 0.01 weight part or more, 0.05 weight part or more, 0.1 weight part or more, 0.2 weight part or more or 0.3 weight part or more. In another example, relative to the acrylic polymer component of 100 weight parts, the curable composition can include a metal catalyst with 1 weight part or less, 0.8 weight part or less, 0.6 weight part or less or 0.4 weight part or less. The content ratio of the metal catalyst included in the curable composition can be included in the scope formed by appropriately selecting the upper and lower limits listed above. When the content ratio of the metal catalyst included in the curable composition satisfies the above scope, a curable composition having guaranteed enough curability and storage stability can be formed, and a cured product having guaranteed suitable bonding force can be formed.
[0173] The curable composition according to one example of the present application can establish a room temperature initiation and curing system by introducing a redox reaction of a peroxide compound and a metal catalyst. In particular, considering the acrylic monomer component containing a cyclic ether-based acrylic compound, it is preferred to use a ketone peroxide compound as the peroxide compound and use a metal naphthenic acid as the metal catalyst.
[0174] If necessary, the curable composition according to one example of the present application may further include a plasticizer. The type of the plasticizer is not particularly limited, but for example, one or more of the following may be selected and used: phthalic acid compounds, phosphoric acid compounds, adipic acid compounds, sebacic acid compounds, citric acid compounds, glycolic acid compounds, trimellitic acid compounds, polyester compounds, epoxidized soybean oil, chlorinated paraffin, chlorinated fatty acid esters, fatty acid compounds, compounds having a saturated aliphatic chain substituted with a sulfonic acid group bonded to a phenyl group (e.g., mesamoll of LANXESS), and vegetable oils.
[0175] As the phthalic acid compound, one or more of the following can be used: dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dihexyl phthalate, di-n-octyl phthalate, di-2-ethylhexyl phthalate, diisooctyl phthalate, dioctyl phthalate, dinonyl phthalate, diisononyl phthalate, didecyl phthalate, diundecyl phthalate, dilauryl phthalate, ditridecyl phthalate, dibenzyl phthalate, dicyclohexyl phthalate, butyl benzyl phthalate, octyl decyl phthalate, butyl octyl phthalate, octyl benzyl phthalate, n-hexyl-n-decyl phthalate, n-octyl phthalate and n-decyl phthalate. As the phosphoric acid compound, one or more of the following can be used: tricresyl phosphate, trioctyl phosphate, triphenyl phosphate, octyl diphenyl phosphate, cresyl diphenyl phosphate and trichloroethyl phosphate. As the adipic acid compound, one or more of the following can be used: dibutoxyethoxyethyl adipate (DBEEA), dioctyl adipate, diisooctyl adipate, di-n-octyl adipate, didecyl adipate, diisononyl adipate (DINA), diisodecyl adipate (DIDP), n-octyl n-decyl adipate, n-heptyl adipate and n-nonyl adipate. As the sebacic acid compound, one or more of dibutyl sebacate, dioctyl sebacate, diisooctyl sebacate and butyl benzyl can be used. As the citric acid compound, one or more of triethyl citrate, acetyl triethyl citrate, tributyl citrate, acetyl tributyl citrate and acetyl trioctyl citrate can be used. As the glycolic acid compound, one or more of glycolic acid methyl phthalyl ethyl ester, glycolic acid ethyl phthalyl ethyl ester and glycolic acid butyl phthalyl ethyl ester can be used. As the trimellitic acid compound, one or more of trimellitic acid trioctyl ester and trimellitic acid tri-n-octyl-n-decyl ester can be used. The polyester compound can be a reaction product of a diol selected from butanediol, ethylene glycol, propane 1,2-diol, propane 1,3-diol, polyethylene glycol, glycerol, a diacid (selected from adipic acid, succinic acid and succinic anhydride) and a hydroxy acid (such as hydroxystearic acid).
[0176] If necessary, the curable composition according to one example of the present application may further include a dispersant. The dispersant may improve the dispersibility of the filler composition in the curable composition.
[0177] As the dispersant, for example, polyamidoamines and salts thereof, polycarboxylic acids and salts thereof, modified polyurethanes, modified polyesters, modified poly(meth)acrylates, (meth)acrylic acid copolymers, naphthalenesulfonic acid formalin condensates, polyoxyethylene alkyl phosphates, polyoxyethylene alkylamines and pigment derivatives can be used, but any dispersant known in the art can be used without limitation.
[0178] If necessary, the curable composition according to an example of the present application may further include a reaction accelerator. The reaction accelerator may perform the function of promoting the polymerization reaction of the curable composition. The type of reaction accelerator is not particularly limited, but for example, one or more selected from amine-based compounds (N,N-dimethylaniline and N,N-dimethyl-p-toluidine (DMPT) etc.), saccharin-based compounds and hydrazine-based compounds may be used.
[0179] If necessary, the curable composition according to an example of the present application may include a viscosity modifier, such as a thixotropic agent, a diluent, a surface treatment agent or a coupling agent, etc., for controlling viscosity, such as increasing or reducing viscosity, or for controlling viscosity according to shear force. A thixotropic agent can adjust the viscosity of the curable composition according to shear force, and available thixotropic agents can be exemplified as pyrogenic silica, etc. A diluent is generally used to reduce the viscosity of the curable composition, and as long as it can show such an effect, various types of diluents known in the art can be used without restriction. A surface treatment agent is used for the surface treatment of the filler composition introduced into the cured product of the curable composition, and as long as it can show such an effect, various types known in the art can be used without restriction. A coupling agent can be used, for example, to improve the dispersibility of thermally conductive filler particles (e.g., aluminum oxide, etc.), and as long as it can show such an effect, various types known in the art can be used without restriction.
[0180] If necessary, the curable composition according to an example of the present application may also include a flame retardant or a flame retardant aid. The curable composition also including a flame retardant or a flame retardant aid can be cured to form a flame retardant cured product. As a flame retardant, various known flame retardants can be applied without particular restriction, for example, a flame retardant in the form of a solid filler or a liquid flame retardant can be applied. Flame retardants include, for example, organic flame retardants such as melamine cyanurate / salt or inorganic flame retardants such as magnesium hydroxide, but are not limited thereto. When the amount of thermally conductive filler particles included in the curable composition is large, liquid flame retardant materials (TEP, triethyl phosphate, or TCPP, tris (1,3-chloro-2-propyl) phosphate, etc.) can also be used. In addition, a silane coupling agent that can act as a flame retardant synergist can also be added.
[0181] The curable composition according to an example of the present application can be a one-component type or a two-component type. As known in the art, the term one-component type as used herein means a form of a cured product that can be formed in a state where the main part and the curing agent part are mixed together. In addition, as known therein, the term two-component type as used herein means a form of a cured product that can be formed by separating the main part and the curing agent part, mixing them and reacting them.
[0182] In addition, when the curable composition according to one example of the present application is a two-component type, it can be divided into a main part and a curing agent part according to the type of additives. The main part may further include a peroxide compound, and the curing agent part may further include a metal catalyst.
[0183] Cured product of curable composition
[0184] As described above, the curable composition according to one example of the present application may be active energy ray (eg, ultraviolet) curable, moisture curable, heat curable or room temperature curable. Preferably, the curable composition may be a room temperature curable composition.
[0185] The curable composition according to an example of the present application can be cured according to the above method to form a cured product, and can have at least one or more of the following physical properties. Each of the physical properties described below is independent, wherein any one physical property does not take precedence over other properties, and the cured product of the curable composition can satisfy at least one or two or more of the physical properties described below. The cured product of the curable composition that satisfies at least one or two or more of the physical properties described below is caused by the combination of each component in the curable composition.
[0186] The curable composition according to one example of the present application can be properly cured within 6 hours after curing initiation at room temperature, wherein it can be evaluated as excellent in curing efficiency. In addition, the curable composition according to one example of the present application in a high humidity environment (about 70RH% or more) and at room temperature after curing initiation after 4 hours immediately measured viscosity (Va) and the viscosity (Vb) measured at the time of curing initiation ratio (Va / Vb) can be about 10,000 or more, wherein it can be evaluated as excellent in curing efficiency.
[0187] When the ratio (V1 / V2) of the viscosity (V1) measured after curing to the viscosity (V2) measured when curing is initiated is about 10,000 or more, 10,500 or more, 11,000 or more, 11,500 or more, or 12,000 or more, the curable composition according to an example of the present application can be considered to be cured. Here, the time taken for curing to meet the ratio (V1 / V2) can be considered as the curing time. As described above, the curing time can be 6 hours or less, 5 hours or less, or 4 hours or less.
[0188] The curable composition according to one example of the present application may generate heat when cured. In order to prevent thermal damage to battery cells or electronic components to which the cured product of the curable composition can be applied due to the curing of the curable composition, it may be appropriate that the exothermic temperature of the curable composition does not exceed about 50°C.
[0189] When the curable composition is prepared as a sample (cured product) having a diameter of 2 cm or more and a thickness of 500 μm, the thermal conductivity of the cured product of the curable composition according to one example of the present application measured along the thickness direction of the sample according to the ASTM D5470 standard or the ISO22007-2 standard can be about 1.2 W / mK or more. In another example, the thermal conductivity of the cured product of the curable composition may also be about 1.3 W / mK or more, 1.4 W / mK or more, 1.5 W / mK or more, 1.6 W / mK or more, 1.7 W / mK or more, 1.8 W / mK or more, 1.9 W / mK or more, 2.0 W / mK or more, 2.1 W / mK or more, 2.2 W / mK or more, 2.3 W / mK or more, 2.4 W / mK or more, 2.5 W / mK or more, 2.6 W / mK or more, 2.7 W / mK or more, 2.8 W / mK or more, 2.9 W / mK or more, or 3.0 W / mK or more. When the thermal conductivity has a high value, it means high thermal conductivity, so that its upper limit is not particularly limited. For example, the thermal conductivity of the cured product of the curable composition may be 20 W / mK or less, 18 W / mK or less, 16 W / mK or less, 14 W / mK or less, 12 W / mK or less, 10 W / mK or less, 8 W / mK or less, 6 W / mK or less, or 4 W / mK or less.
[0190] The thermal resistance of the cured product of the curable composition according to an example of the present application can be about 5K / W or less, about 4.5K / W or less, about 4K / W or less, about 3.5K / W or less, about 3K / W or less, or about 2.8K / W or less. When it is adjusted so that a thermal resistance within the range can be presented, excellent cooling efficiency or heat dissipation efficiency can be ensured. Thermal resistance can be a value measured according to ASTM D5470 standard or ISO 22007-2 standard, and the measuring method is not particularly limited.
[0191] The cured product of the curable composition according to one example of the present application may have an adhesion (or peel force) to a PET (polyethylene terephthalate) film of about 600 kgf / cm or more, 625 kgf / cm or more, 650 kgf / cm or more, 675 kgf / cm or more, 700 kgf / cm or more, 725 kgf / cm or more, 750 kgf / cm or more, 775 kgf / cm or more, about 800 kgf / cm or more, 810 kgf / cm or more, 820 kgf / cm or more, 830 kgf / cm or more, 840 kgf / cm or more, or 850 kgf / cm or more. In another example, the adhesive force (or peeling force) of the cured product of the curable composition to PET (polyethylene terephthalate) film can be about 1,500kgf / cm or less, about 1,400kgf / cm or less, about 1,300kgf / cm or less, about 1,200kgf / cm or less, or about 1,150kgf / cm or less. In the cured product of the curable composition, the adhesive force (or peeling force) to PET (polyethylene terephthalate) film can be included in the range formed by appropriately selecting the upper and lower limits listed above. Here, the adhesive force (or peeling force) can be the value measured at room temperature using an adhesive force measuring device (or a physical property measuring device capable of measuring adhesive force) at a peeling rate of 300mm / min and a peeling angle of 180 degrees. Adhesive force can be specifically measured according to the following method for measuring physical properties.
[0192] In addition, the adhesive force may be an adhesive force to any substrate or module housing in contact with the cured product of the curable composition. If such an adhesive force can be ensured, excellent adhesive force can be exhibited for various materials such as a housing or a battery cell included in a battery module. In addition, if an adhesive force within the range is ensured, peeling caused by volume changes during charging and discharging of the battery cell in the battery module, changes in the use temperature of the battery module, or curing shrinkage, etc., is prevented, thereby ensuring excellent durability.
[0193] The cured product of the curable composition according to one example of the present application can ensure durability to be applied to products such as automobiles that require a long shelf life (in the case of automobiles, about 15 years or longer). Durability can mean that after a cycle is set to keep the temperature at a low temperature of about -40°C for 30 minutes and then raise the temperature to 80°C and keep it for 30 minutes, and repeating a thermal shock test for 100 cycles, there will be no separation or peeling or cracking from the module housing or battery cell of the battery module.
[0194] The electrical insulation of the cured product of the curable composition according to an example of the present application can be about 3kV / mm or more, about 5kV / mm or more, about 7kV / mm or more, 10kV / mm or more, 15kV / mm or more, or 20kV / mm or more. When the dielectric breakdown voltage has a higher value, the cured product of the curable composition shows excellent insulation, wherein it can be about 50kV / mm or less, 45kV / mm or less, 40kV / mm or less, 35kV / mm or less, or 30kV / mm or less, but there is no particular limitation. In order to achieve such a dielectric breakdown voltage, an insulating filler can be applied to the curable composition. Generally, in thermally conductive fillers, ceramic fillers are referred to as components that can ensure insulation. Electrical insulation can be measured with a dielectric breakdown voltage measured according to ASTMD149 standards. In addition, if the cured product of the curable composition can ensure electrical insulation as above, then for various materials such as the housing or battery cells included in the battery module, stability can be ensured while maintaining performance.
[0195] The specific gravity of the cured product of the curable composition according to an example of the present application can be 5 or less. In another example, the specific gravity can be 4.5 or less, 4 or less, 3.5 or less, or 3 or less. When the specific gravity of the cured product of the curable composition has a lower value, it is more conducive to the weight loss of the applied product, so that its lower limit is not particularly limited. For example, the specific gravity can be about 1.5 or greater, or 2 or greater. In order to make the cured product of the curable composition show such a specific gravity, for example, a filler (that is, a filler with a low specific gravity itself) that can ensure the desired thermal conductivity even at a low specific gravity can be used when adding a thermally conductive filler or a method of applying a surface-treated filler, etc.
[0196] If possible, it is suitable that the cured product of the curable composition according to an example of the present application does not include volatile materials. For example, in the cured product of the curable composition, the ratio of non-volatile components can be 90% by weight or more, 95% by weight or more, or 98% by weight or more. Here, the ratio of non-volatile components can be defined in the following manner. That is, with respect to non-volatile content, the remaining part after the cured product of the curable composition is maintained at 100°C for about 1 hour can be defined as non-volatile content, so the ratio can be based on the ratio of the initial weight of the cured product of the curable composition after the cured product of the curable composition is maintained at 100°C for about 1 hour to the cured product of the curable composition.
[0197] If necessary, a cured product of the curable composition according to one example of the present application may have excellent resistance to degradation, wherein stability without chemical reaction may be required if possible.
[0198] It may be advantageous for the cured product of the curable composition according to one example of the present application to have a low shrinkage during or after curing. Thus, peeling or gaps that may occur during the manufacture or use of various materials such as a housing or battery cell included in a battery module can be prevented. The shrinkage rate can be appropriately adjusted within the range that can show the above-mentioned effect, which may be, for example, less than 5%, less than 3%, or less than about 1%. Since the shrinkage rate is more favorable when the value is lower, its lower limit is not particularly limited.
[0199] The cured product of the curable composition according to an example of the present application may also advantageously have a low coefficient of thermal expansion (CTE). Thus, it is possible to prevent peeling or gaps that may occur in the process of manufacturing or using various materials such as the housing or battery cell included in the battery module. The thermal expansion coefficient can be appropriately adjusted within the range that can show the above-mentioned effect, and it can be, for example, less than 300ppm / K, less than 250ppm / K, less than 200ppm / K, less than 150ppm / K or less than 100ppm / K. Since the thermal expansion coefficient is more favorable when the value is lower, its lower limit is not particularly limited.
[0200] In the cured product of the curable composition according to one example of the present application, the tensile strength can be appropriately adjusted, and thereby, excellent impact resistance, etc. can be ensured. The tensile strength can be adjusted, for example, within a range of about 1.0 MPa or more.
[0201] In the cured product of the curable composition according to one example of the present application, the elongation can be appropriately adjusted, and thus, excellent impact resistance can be ensured. The elongation can be adjusted, for example, within a range of about 10% or more or about 15% or more.
[0202] It may be advantageous that the cured product of the curable composition of an example of the present application also shows appropriate hardness. As used herein, the term appropriate hardness can be the hardness that the cured product of the curable composition is not evaluated as brittle. When the hardness of the cured product of the curable composition is too high, the cured product of the curable composition is excessively brittle, which may adversely affect reliability. In addition, by adjusting the hardness, it is possible to ensure impact resistance and vibration resistance, and it is possible to ensure the durability of the product.
[0203] A cured product of the curable composition according to one example of the present application was produced to have a width of about 10 cm, a length of about 20 cm, and a thickness of about 2 mm, and then checked whether it broke in the form of powder when scraped with tweezers, wherein the case of no breakage can be evaluated as not being brittle.
[0204] In addition, the cured product of curable composition can have, for example, a Shore A hardness less than 100, 99 or less, 98 or less, 95 or less, or 93 or less, or can have a Shore D hardness less than about 80, less than about 70, or about 65 or less, or about 60 or less. The lower limit of hardness is not particularly limited. For example, about hardness, the Shore A hardness can be about 60 or more, or the Shore OO hardness can be 5 or more or about 10 or more. The hardness of the cured product of curable composition depends on the type and ratio of the filler included in the resin layer generally, and when comprising excessive filler, hardness increases generally.
[0205] In the cured product of the curable composition according to one example of the present application, the 5% weight loss temperature in the thermogravimetric analysis (TGA) may also be 400°C or higher, or the remaining amount at 800°C may be 70 wt% or more. Due to these characteristics, the stability at high temperatures can be further improved for various materials such as housings or battery cells included in battery modules. In another example, the remaining amount at 800°C may be about 75 wt% or more, about 80 wt% or more, about 85 wt% or more, or about 90 wt% or more. In another example, the remaining amount at 800°C may be about 99 wt% or less. Thermogravimetric analysis (TGA) can be performed at 60 cm 3 / minute nitrogen (N2) atmosphere at a heating rate of 20 ° C / minute in the range of 25 ° C to 800 ° C. Thermogravimetric analysis (TGA) results can also be achieved by adjusting the composition of the cured product of the curable composition. For example, the remaining amount at 800 ° C depends on the type or ratio of the thermally conductive filler included in the cured product of the curable composition, and when an excess of thermally conductive filler is included, the remaining amount increases. However, when the polymer and / or monomer used in the curable composition generally has high heat resistance compared to other polymers and / or monomers, the remaining amount increases more, and therefore the polymer and / or monomer components included in the cured product of the curable composition also affect the hardness.
[0206] The mixing order of the curable composition according to one example of the present application is not particularly limited as long as all necessary components such as filler, acrylic monomer component and acrylic polymer component can be included. As described above, the acrylic polymer component can be formed by polymerizing an acrylic polymer precursor composition.
[0207] use
[0208] The device according to one example of the present application may be a device including an exothermic element and a cooling region, wherein a cured product of the curable composition according to one example of the present application is included between the exothermic element and the cooling region in thermal contact with both.
[0209] The device according to an example of the present application includes, for example, various electrical products and electronic products, such as clothes irons, washing machines, dryers, clothes managers, electric shavers, microwave ovens, electric stoves, rice cookers, refrigerators, dishwashers, air conditioners, fans, humidifiers, air purifiers, mobile phones, wireless telegraphs, televisions, radios, computers and laptops; or batteries, such as secondary batteries, wherein the cured product of the curable composition can emit the heat generated in the device. In particular, in an electric vehicle battery manufactured by aggregating battery cells to form a battery module and combining several battery modules to form a battery pack, the curable composition of the present application can be used as a material for connecting battery modules. When the curable composition of the present application is used as a material for connecting battery modules, the curable composition of the present application can play a role in dissipating the heat generated in the battery cell and fixing the battery cell from external shock and vibration.
[0210] The cured product of the curable composition of the present application can transfer the heat generated by the exothermic element to the cooling area. That is, the cured product of the curable composition can dissipate the heat generated by the exothermic element.
[0211] The cured product of the curable composition can be positioned between the exothermic element and the cooling zone so that they are in thermal contact. Thermal contact means that the cured product of the curable composition is in direct physical contact with the exothermic element and the cooling zone to dissipate the heat generated by the exothermic element to the cooling zone, or even if the cured product of the curable composition is not in direct contact with the exothermic element and the cooling zone (i.e., there is a separate layer between the cured product of the curable composition and the exothermic element and / or the cooling zone), the cured product of the curable composition dissipates the heat generated by the exothermic element to the cooling zone.
[0212] Beneficial Effects
[0213] The present application can provide a curable composition capable of ensuring excellent storage stability regardless of environmental changes by having excellent resistance to moisture and humidity.
[0214] Furthermore, the present application can provide a curable composition that exhibits room temperature curability and rapid curability in a high humidity environment even if an excessive amount of a filler composition is included.
[0215] Furthermore, the present application can provide a curable composition that exhibits appropriate viscosity, thixotropy, adhesion, and / or thermal conductivity before and after curing.
[0216] Furthermore, the present application can provide a curable composition capable of forming a cured product that is not brittle and is flexible by adjusting hardness. DETAILED DESCRIPTION
[0217] Hereinafter, the present application will be described through Examples and Comparative Examples, but the scope of the present application is not limited to the contents presented below.
[0218] Example 1
[0219] Into a 2L glass reactor, an acrylic polymer precursor composition formed by mixing tetrahydrofurfuryl methacrylate (THFMA), acrylamide (AA), 2-hydroxyethyl acrylate (2-HEA), and 1-dodecyl mercaptan (DM) as a molecular weight regulator at a weight ratio of 100:6.59:3.30:6.59 (THFMA:AA:2-HEA:DM) was introduced. Thereafter, the glass reactor was purged with nitrogen and the temperature was simultaneously raised from room temperature to about 62°C over 1 hour. Thereafter, when the temperature of the reactor reached about 62°C, about 0.0047% by weight of a polymerization initiator (2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (V-70, Fujifilm) was introduced into the reactor relative to the total weight of the acrylic polymer precursor composition and reacted at a reaction temperature not exceeding about 70°C. During the polymerization reaction, the polymerization initiator was further introduced three times in the same amount, so that the total number of initiations was four times. The polymerization reaction is carried out until it has an appropriate weight average molecular weight, and a reaction composition (R) containing an acrylic polymer component having a weight average molecular weight of about 7,000 g / mol is prepared. At this time, the reaction composition (R) contains 46.13% by weight of the acrylic polymer component (i.e., the conversion rate is 46.13%), and the viscosity of the acrylic polymer component measured at room temperature is 1,850 cP. The conversion rate is calculated by collecting a specific mass of the reaction composition (R), placing it on an aluminum plate, placing it in an oven preheated to about 150° C. to dry it for 50 minutes, and then using the weight difference between the dried reaction composition (R′) and the reaction composition (R). In addition, in the present application, the conversion rate of the reaction composition (R) is measured as described above.
[0220] Here, the reaction composition (R), tetrahydrofurfuryl methacrylate (THFMA) and 2-hydroxyethyl acrylate (2-hydroxypropyl methacrylate, 2-HPMA) were mixed in a weight ratio of 100:43.20:10.80 (R:THFMA:2-HPMA) to prepare a primary mixture (M1) (solid content about 30%).
[0221] A filler composition (F) was prepared by mixing flaky aluminum oxide (F1) having an average particle size of about 1.6 μm, spherical aluminum oxide (F2) having an average particle size of about 70 μm, and aluminum hydroxide (F3) having an average particle size of about 50 μm in a weight ratio of 360:360:180 (F1:F2:F3).
[0222] Here, the primary mixture (M1) and the filler composition (F) are mixed in a weight ratio of 1:9 (M1:F) to prepare a secondary mixture (M2), and about 6.68 parts by weight of methyl ethyl ketone peroxide (MEKP) relative to 100 parts by weight of the acrylic polymer component and about 0.33 parts by weight of cobalt naphthalene dicarboxylic acid relative to 100 parts by weight of the acrylic polymer component are further added to the secondary mixture (M2) to prepare a final curable composition (P).
[0223] Example 2
[0224] A reaction composition (R) containing an acrylic polymer component having a weight average molecular weight of about 7,000 g / mol was prepared in the same manner as in Example 1 above, except that the polymerization initiator was introduced once more during the polymerization reaction, whereby the total number of initiations was 5 times. The reaction composition (R) was prepared. At this time, the reaction composition (R) contained 60.13% by weight of the acrylic polymer component (i.e., the conversion rate was 60.13%), and the viscosity of the acrylic polymer component measured at room temperature was 5,400 cP.
[0225] Here, the reaction composition (R), tetrahydrofurfuryl methacrylate (THFMA) and 2-hydroxyethyl acrylate (2-hydroxypropyl methacrylate, 2-HPMA) were mixed in a weight ratio of 100:16:4 (R:THFMA:2-HPMA) to prepare a primary mixture (M1) (solid content about 50%).
[0226] As the filler composition (F), the same filler composition (F) as that prepared in Example 1 above was used.
[0227] Here, the primary mixture (M1) and the filler composition (F) are mixed in a weight ratio of 1:9 (M1:F) to prepare a secondary mixture (M2), and about 6.68 parts by weight of methyl ethyl ketone peroxide (MEKP) relative to 100 parts by weight of the acrylic polymer component and about 0.33 parts by weight of cobalt naphthalene dicarboxylic acid relative to 100 parts by weight of the acrylic polymer component are further added to the secondary mixture (M2) to prepare a final curable composition (P).
[0228] Example 3
[0229] The final curable composition (P) was prepared in the same manner as in Example 1 above, except that a reaction composition (R) having a weight average molecular weight of about 13,000 g / mol and containing 46.13 wt % of an acrylic polymer component (i.e., a conversion rate of 46.13%) was prepared, although it was prepared in the same manner as in Example 1 above.
[0230] Example 4
[0231] The final curable composition (P) was prepared in the same manner as in Example 2 above, except that a reaction composition (R) having a weight average molecular weight of about 13,000 g / mol and containing 60.13 wt % of an acrylic polymer component (i.e., a conversion rate of 60.13%) was prepared, although it was prepared in the same manner as in Example 2 above.
[0232] Comparative Example 1
[0233] Tetrahydrofurfuryl methacrylate (THFMA) and 2-hydroxyethyl acrylate (2-hydroxypropyl methacrylate, 2-HPMA) were mixed at a weight ratio of 80:20 (THFMA:2-HPMA) to prepare a primary mixture (M1).
[0234] A filler composition (F) was prepared by mixing flaky aluminum oxide (F1) having an average particle size of about 1.6 μm, spherical aluminum oxide (F2) having an average particle size of about 70 μm, and aluminum hydroxide (F3) having an average particle size of about 50 μm in a weight ratio of 360:360:180 (F1:F2:F3).
[0235] Here, the primary mixture (M1) and the filler composition (F) are mixed in a weight ratio of 1:9 (M1:F) to prepare a secondary mixture (M2), and about 2 parts by weight of methyl ethyl ketone peroxide (MEKP) relative to 100 parts by weight of the primary mixture (M1) and about 0.1 parts by weight of cobalt naphthalene dicarboxylic acid relative to 100 parts by weight of the primary mixture (M1) are further added to the secondary mixture (M2) to prepare a final curable composition (P).
[0236] Comparative Example 2
[0237] A secondary mixture (M2) was prepared by mixing the reaction composition (R) and the filler composition (F) prepared in the same manner as in Example 2 above in a weight ratio of 1:9 (R:F), and about 6.68 parts by weight of methyl ethyl ketone peroxide (MEKP) relative to 100 parts by weight of the acrylic polymer component and about 0.33 parts by weight of cobalt naphthalene dicarboxylic acid relative to 100 parts by weight of the acrylic polymer component were further added to the secondary mixture (M2) to prepare a final curable composition (P).
[0238] Comparative Example 3
[0239] The reaction composition (R) prepared in the same manner as in Example 1 above, tetrahydrofurfuryl methacrylate (THFMA) and 2-hydroxyethyl acrylate (2-hydroxypropyl methacrylate, 2-HPMA) were mixed in a weight ratio of 100:104:26 (R:THFMA:2-HPMA) to prepare a primary mixture (M1) (solid content about 20%).
[0240] As the filler composition (F), the same filler composition (F) as that prepared in Example 1 above was used.
[0241] Here, the primary mixture (M1) and the filler composition (F) are mixed in a weight ratio of 1:9 (M1:F) to prepare a secondary mixture (M2), and about 6.68 parts by weight of methyl ethyl ketone peroxide (MEKP) relative to 100 parts by weight of the acrylic polymer component and about 0.33 parts by weight of cobalt naphthalene dicarboxylic acid relative to 100 parts by weight of the acrylic polymer component are further added to the secondary mixture (M2) to prepare a final curable composition (P).
[0242] Comparative Example 4
[0243] The final curable composition (P) was prepared in the same manner as in Example 1 above, except that a reaction composition (R) having a weight average molecular weight of about 15,000 g / mol and containing 46.13 wt % of an acrylic polymer component (i.e., a conversion rate of 46.13%) was prepared, although it was prepared in the same manner as in Example 1 above.
[0244] Comparative Example 5
[0245] A reaction composition (R) prepared in the same manner as in Example 1 above, tetrahydrofurfuryl methacrylate (THFMA) and 2-hydroxyethyl acrylate (2-hydroxypropyl methacrylate, 2-HPMA) were mixed in a weight ratio of 100:7380.8:1845.2 (R:THFMA:2-HPMA) to prepare a primary mixture (M1) (solid content of about 0.5%).
[0246] As the filler composition (F), the same filler composition (F) as that prepared in Example 1 above was used.
[0247] Here, the primary mixture (M1) and the filler composition (F) are mixed in a weight ratio of 1:9 (M1:F) to prepare a secondary mixture (M2), and about 6.68 parts by weight of methyl ethyl ketone peroxide (MEKP) relative to 100 parts by weight of the acrylic polymer component and about 0.33 parts by weight of cobalt naphthalene dicarboxylic acid relative to 100 parts by weight of the acrylic polymer component are further added to the secondary mixture (M2) to prepare a final curable composition (P).
[0248] Comparative Example 6
[0249] The reaction composition (R) prepared in the same manner as in Example 1 above, tetrahydrofurfuryl methacrylate (THFMA) and 2-hydroxyethyl acrylate (2-hydroxypropyl methacrylate, 2-HPMA) were mixed in a weight ratio of 100:1476.16:369.04 (R:THFMA:2-HPMA) to prepare a primary mixture (M1) (solid content about 2.37%).
[0250] As the filler composition (F), the same filler composition (F) as that prepared in Example 1 above was used.
[0251] Here, the primary mixture (M1) and the filler composition (F) are mixed in a weight ratio of 1:9 (M1:F) to prepare a secondary mixture (M2), and about 6.68 parts by weight of methyl ethyl ketone peroxide (MEKP) relative to 100 parts by weight of the acrylic polymer component and about 0.33 parts by weight of cobalt naphthalene dicarboxylic acid relative to 100 parts by weight of the acrylic polymer component are further added to the secondary mixture (M2) to prepare a final curable composition (P).
[0252] <Methods of measuring physical properties>
[0253] (1) Method for evaluating curing efficiency of curable composition
[0254] For each of the curable compositions (P) prepared in the above Examples and Comparative Examples, the ratio (Va / Vb) of the viscosity (Va) measured immediately after 4 hours after the initiation of curing at room temperature in a high humidity environment (about 70 RH% or more) and the viscosity (Vb) measured at the time of initiation of curing was measured. If the ratio (Va / Vb) of the viscosity is 10,000 or more, it is evaluated as O (excellent curing efficiency), and if it is less than 10,000, it is evaluated as X (inappropriate curing efficiency). The viscosity is measured using a Brookfield AMETEK / DV3T using a spindle 63.
[0255] (2) Adhesion evaluation method
[0256] A glass substrate with a thickness of 1 mm is prepared, and two glass baffles with a thickness of 2 mm are installed so that a predetermined gap is formed on the glass substrate. Each curable composition (P) prepared in the above embodiment and comparative example is uniformly applied to the predetermined gap formed by the glass baffle so that no bubbles are generated. An aluminum bag in which a PET (polyethylene terephthalate) interface is present is cut to have a width of 10 mm and a length of 200 mm, and then attached thereto so that the PET interface of the aluminum bag contacts the applied curable composition (P). Thereafter, after attaching the release paper, a glass plate is placed on the release paper so that the curable composition (P) is subjected to sufficient pressure and placed at room temperature for about 24 hours, and then the placed glass plate and release film are removed. Thereafter, the attached aluminum bag is peeled off at a peeling angle of 180 degrees and a speed of 300 mm / min with a physical property measuring device (manufacturer: stable micro systems, texture analyzer), and the adhesion of the cured product of the curable composition (P) is measured.
[0257] (3) Brittleness assessment method
[0258] The cured products of each curable composition (P) prepared in the Examples and Comparative Examples were cured in a high humidity environment (about 70 RH% or more) and at room temperature to have a width of about 10 cm, a length of about 20 mm and a thickness of about 2 mm, and then checked whether they were broken in the form of powder when scraped with tweezers, wherein the case of no breakage was evaluated as O (not brittle), and the case of breakage was evaluated as X (brittle).
[0259] (4) Thermal conductivity evaluation method
[0260] The thermal conductivity was measured using a hot disk method. Specifically, in a state where each of the curable compositions (P) prepared in the above Examples and Comparative Examples was cured into a disk-shaped sample having a diameter of 2 cm and a thickness of 500 μm, the thermal conductivity was measured along the thickness direction of the sample using a thermal analysis device (thermal constant analyzer) according to ISO 22007-2 standard.
[0261] The results of the test data measured in the above Examples and Comparative Examples are summarized in Table 1 below.
[0262] [Table 1]
[0263]
[0264] As shown in Table 1, it can be seen that Examples 1 to 4 exhibit excellent curing efficiency even at room temperature and under a high humidity environment, ensure the desired adhesive force and thermal conductivity in the present application, and are not brittle.
[0265] On the other hand, it can be seen that Comparative Examples 1 and 2 were cured within 24 hours under room temperature and high humidity environment, but the cured products were brittle because they had low adhesive force and flexibility was not ensured.
[0266] Furthermore, in Comparative Examples 3 to 6, mixing between the components of the curable composition could not be performed, and thus curing could not be performed. Furthermore, a cured product could not be formed, so that adhesion, brittleness, and thermal conductivity could not be evaluated.
Claims
1. A curable composition comprising a filler composition, an acrylic monomer component and an acrylic polymer component; wherein one or more of the polymerization units selected from the acrylic polymer component and the acrylic monomer component comprises a cyclic ether-based acrylic compound, wherein the acrylic monomer component is contained in a range of 70 parts by weight to 380 parts by weight relative to 100 parts by weight of the acrylic polymer component, wherein the weight average molecular weight of the acrylic polymer component is in the range of 1,000 g / mol to 14,500 g / mol, The cyclic ether-based acrylic acid compound includes a compound represented by the following Formula 2: [Formula 2] in, R 3 is hydrogen or an alkyl group having 1 to 20 carbon atoms, L 1 and L 2 are each independently a single bond or an alkylene group, and L 3 is an alkylene group, and The curable composition forms a cured product having a thermal conductivity of 1.2 W / mK or more. 2 . The curable composition according to claim 1 , comprising the acrylic polymer component in an amount ranging from 2.5 wt % to 5.5 wt % relative to the total weight. 3 . The curable composition according to claim 1 , comprising the filler composition in an amount ranging from 1,000 parts by weight to 6,000 parts by weight relative to 100 parts by weight of the acrylic polymer component.
4. The curable composition according to claim 1, wherein in Formula 2, R 3 is an alkyl group having 1 to 20 carbon atoms, L 1 is an alkylene group, L 2 is a single bond, and L 3 It is an alkylene group.
5. The curable composition according to claim 1, wherein in Formula 2, L 2 and L 3 The sum of the number of carbon atoms present in is in the range of 1 to 8. 6 . The curable composition according to claim 1 , wherein the polymerization unit of the acrylic polymer component comprises the cyclic ether-based acrylic compound in an amount of 70 wt % or more relative to the total weight. 7 . The curable composition according to claim 1 , wherein polymerization units of the acrylic polymer component comprise the cyclic ether-based acrylic compound and a hydroxyl group-containing acrylic compound. 8 . The curable composition according to claim 7 , wherein the polymerization unit of the acrylic polymer component includes the hydroxyl group-containing acrylic compound in a range of 0.1 parts by weight to 10 parts by weight relative to 100 parts by weight of the cyclic ether-based acrylic compound.
9. The curable composition according to claim 7, wherein the hydroxyl-containing acrylic compound comprises a compound represented by the following Formula 3: [Formula 3] in, R 4 is hydrogen or an alkyl group having 1 to 20 carbon atoms, L 4 is one selected from the group consisting of an alkylene group having 1 to 20 carbon atoms, an alkenylene group having 2 to 20 carbon atoms, an alkynylene group having 2 to 20 carbon atoms, an arylene group having 6 to 30 carbon atoms, and a heteroarylene group having 5 to 30 ring atoms. 10 . The curable composition according to claim 1 , wherein polymerization units of the acrylic polymer component comprise the cyclic ether-based acrylic compound and acrylamide. 11 . The curable composition according to claim 10 , wherein the polymerization unit of the acrylic polymer component includes the acrylamide in a range of 1 to 30 parts by weight relative to 100 parts by weight of the cyclic ether-based acrylic compound.
12. The curable composition of claim 1, wherein polymerized units of the acrylic polymer component contain substantially no aromatic compounds. 13 . The curable composition according to claim 1 , wherein the acrylic monomer component includes the cyclic ether-based acrylic compound in an amount of 60 wt % or more relative to the total weight of the acrylic monomer component. 14 . The curable composition according to claim 1 , wherein the acrylic monomer component comprises the cyclic ether-based acrylic compound and a hydroxyl group-containing acrylic compound. 15 . The curable composition according to claim 14 , wherein the acrylic monomer component includes the hydroxyl-containing acrylic compound in a range of 1 to 18 parts by weight relative to 100 parts by weight of the cyclic ether-based acrylic compound.
16. The curable composition according to claim 14, wherein the hydroxyl-containing acrylic compound comprises a compound represented by the following Formula 3: [Formula 3] in, R 4 is hydrogen or an alkyl group having 1 to 20 carbon atoms, L 4 is one selected from the group consisting of an alkylene group having 1 to 20 carbon atoms, an alkenylene group having 2 to 20 carbon atoms, an alkynylene group having 2 to 20 carbon atoms, an arylene group having 6 to 30 carbon atoms, and a heteroarylene group having 5 to 30 ring atoms. 17 . The curable composition according to claim 1 , wherein the acrylic monomer component comprises the cyclic ether-based acrylic compound and acrylamide. 18 . The curable composition according to claim 17 , wherein the acrylic monomer component includes the acrylamide in a range of 1 part by weight to 5 parts by weight relative to 100 parts by weight of the cyclic ether-based acrylic compound.
19. The curable composition of claim 1, wherein the acrylic monomer component comprises substantially no aromatic compounds.
20. The curable composition according to claim 1, forming a cured product having a room temperature adhesive force of 600 kgf / cm or more measured at a peel rate of 300 mm / min and a peel angle of 180 degrees with respect to a polyethylene terephthalate film.
21. The curable composition of claim 1, further comprising a peroxide compound and a metal catalyst. 22 . The curable composition according to claim 21 , comprising the peroxide compound in a range of 1 to 10 parts by weight relative to 100 parts by weight of the acrylic polymer component. 23 . The curable composition according to claim 21 , comprising the metal catalyst in a range of 0.01 parts by weight to 1 part by weight relative to 100 parts by weight of the acrylic polymer component.
24. The curable composition according to claim 1, having room temperature curability.
Citation Information
Patent Citations
Battery module
KR1020160105354A
Opening and closing device of machine tool
KR1020200127537A
Acrylic thermal conductive sheet and method for producing the same
CN102307939A
Heat conductive composition, and heat-conductive sheet
JP2012162612A
Heat-dissipating resin composition, substrate for LED mounting, reflector, and substrate for LED mounting having reflector portion
WO2008053753A1
